Reconciling explicit and homogenized modeling strategies for compression behavior of cracked soils - Zhao-Lin Cai; Yu-Jun Cui; Chao-Sheng Tang; Qing Cheng; Zhi-Xiong Zeng; Xin-Lun Ji (Computers and Geotechnics, 2027)

Structure-based virtual screening identifies dicoumarol as a potent InhA inhibitor against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Jin-Lai Gu; Chen-Wang Lu; Lin-Feng Kuang; Jie He; Zheng-Ran Jian; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Zheng-Yang Zhou; Ming-Zhu Liu; Peng-Fei Li; Er-Long Wang; et al. (Aquaculture, 2027)

Application of molasses improves strawberry marketability by enhancing fruit flavor and aroma - Yuanxiu Lin; Yu Long; Zimeng Cui; Siqi Dai; Yunting Zhang; Mengyao Li; Qing Chen; Yong Zhang; Haoru Tang; Yifei Zhou; Ya Luo (Postharvest Biology and Technology, 2026)

Polystyrene nanoparticles impair endometrial decidualization in early pregnant mice via oxidative stress-driven autophagy suppression and ferroptosis induction - Li-Qing Wang; Qian-Feng Qiao; Huang-Nian You; Yi-bin Zheng; Xiao-Mei Wu; Wen-Jie Yu; Zeng Liu; Wen-Juan Song; Lin-Hong Zhang; Jia-Rui Hu; Xin-Yu Mao; Yong-Jiang Zhou (Food and Chemical Toxicology, 2026)

Cyclic regeneration and up-concentration for nitrate recovery from wastewater via in situ NaNO3 generation under saline, fully autotrophic nitrification conditions - Molin Lian; Zihang Ma; Guang Chen; Siqi Yu; Qing Xia; Bingjie Lin; Xiangdong Xu; Rui Tang; Zhen Zhou (Bioresource Technology, 2026)

From astrocyte cholesterol synthesis to synaptic dysfunction: mechanisms of neuron-glia lipid coupling - Muhammad Mateen Tahir; Xiu Liu; Lin-Sheng Yi; Xiao-Qing Hou; Qin Liao; Hua-Li Yu (Molecular Biology Reports, 2026)

Tirzepatide improves neutrophilic inflammation in obese asthmatic mice by downregulating Th17 cell differentiation - Lu Sun; Su-Yan Yao; Zhong-Fu Zuo; Sheng-Xue Yu; Hong-Dan Yu; Qing-Lin Sun; Han-Song Zheng; Yang Hou; Si-Jing Lu; Tie-Feng Yao (Molecular Biology Reports, 2026)

MPP+ disorders Irg1-Itaconate axis to promote M1 polarization of microglia by activating succinate dehydrogenase - Lin-Yu Wang; Yi-Yun Tang; Wei Zou; Ping Zhang; Xiao-Qing Tang; Ping Zhang (Molecular Biology Reports, 2026)

Divergent formation pathways of soil particulate and mineral-associated organic carbon across soil depths under conservation tillage - Hong-Xuan Duan; Yu-Gang Tian; Cheng-Ze Yang; Qing Luo; Yang Liu; Zhi-Yan Hou; Rattan Lal; Yash Pal Dang; Zhi Dong; Xin Zhao; Hai-Lin Zhang (Applied Soil Ecology, 2026)

Bushen Yijing formula exerts chondroprotective effects in knee osteoarthritis via the ERα/PI3K/AKT signaling pathway: Insights from network pharmacology and experimental validation - Yu-Qing Zhai; Jian-Wei Lu; Qiang Yan; Jia-Wei Du; Yang-Shuo Ge; Min-Jun Zhao; Jian-Li Yin; Chun-Meng Huang; Ting-Ting Meng; Xin-Hui Huang; Liao-Lin Chen; Jia-Hui Luo; et al. (Tissue and Cell, 2026)

Interaction of ARA54 with androgen receptor in mediating testosterone-dependent regulation of caput epididymal GPX5 expression in mice - Dong-li Liu; Xin Gao; Yi-ying Wang; Yu-qing Lin; Si-han Yu; Zhao-jin Luan (Theriogenology, 2026)

Fulvic acid-iron colloid promotes the migration of As(III) in porous media - Yanhao Li; Youru Yao; Xinyi Wang; Huimin Zhang; Fengman Fang; Yuesheng Lin; Zhiming Zhang; Qing Ji; Jia Yu (Journal of Contaminant Hydrology, 2026)

Sex peptide receptor modulates sex pheromone perception plasticity in female Galleria mellonella across mating status - Zhen-Ping Guo; Xu-Dong Pang; Li-Lin Luo; Ming-Qing Yu; Jun-Hong Linghu; Hua-Yan Xie; Guy Smagghe; Tong-Xian Liu; Shun-Hua Gui (Insect Biochemistry and Molecular Biology, 2026)

A dual-function electroactive hydrogel platform for mitigating oxidative stress and restoring muscle function - Yi Lin; Zi-Hao Lin; Hai-Bin Jiang; Yu-Hao Kang; Qing-Song Deng; Rong-Tai Zuo; Zhi-Qi Lin; Er-Peng Yang; Jun-Jie Xu; Clara Chen; Xi-Ming Wang; Jin-Zhong Zhao (Chemical Engineering Journal, 2026)

Probe-based near-infrared autofluorescence detection versus carbon nanoparticles for intraoperative parathyroid gland identification in thyroid surgery: A prospective study - Liangyu Gan; Qing Lin; Houjie Liu; Zheng Fang; Wanxue Zhang; Guangjin Yu; Biao Sun; Bin Liu; Yusheng Ye (Chemical Engineering Journal, 2026)

Development of a Recombinant Goose Parvovirus VP2 Neutralizing Epitope-Containing Region Vaccine Adjuvanted with IL-2 and FliC for Enhanced Immune Responses and Protection Against Challenge - Qing Wu; Xinyu Li; Jiaxin Li; Ziran Liu; Lin Bai; Lin Zhang; Shujing Xia; Di Wu; Yuhan Jin; Xinyuan Shen; Yu Gao; Jingming Wang; et al. (The Veterinary Journal, 2026)

Reducing carbon emission commitment constraints of Chinese passenger vehicle manufacturers through life cycle management - Keke Ji; Qing Yang; Zipeng Lin; Yuping Li; Xin Sun; Jiaxin Yu; Xingxing Liu; Liang Dong (Sustainable Production and Consumption, 2026)

Disruption of OsGONST3 reduces grain cadmium accumulation without yield penalty in field-grown rice - Jing Huang; Qiang Zhang; Fang Wei Yu; Ming Qing Liu; Huai Kang Jing; Shen Yun Wang; Hao Yu Wang; Jia Qi Li; Lu Zheng; Hua Shao; Xiao Lin He; Ren Fang Shen; et al. (Journal of Hazardous Materials, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Coupled effect of crack inclination and microstructure on the mechanical behavior of soils - Zhao-Lin Cai; Yu-Jun Cui; Chao-Sheng Tang; Qing Cheng; Zhi-Xiong Zeng; Xin-Lun Ji; Tao Wang; Hao Wang; Hai Wang; Jun-Feng Ren (Engineering Geology, 2026)

Investigating the Antiviral Mechanism of Kaempferol Against Grouper Iridovirus: Combined Evaluation of In Vitro Activity and In Vivo Efficacy - Nijia Xue; Lin Huang; Jieying Yu; Jia Cai; Zhengzhao Liu; Yibing Wang; Shu Cheng; Junxiang Lai; Ying Pan; Qing Yu; Wenhong Li; Pengfei Li (Journal of Fish Diseases, 2026)
Singapore grouper iridovirus (SGIV) is one of the major pathogens that pose significant threats to the aquaculture industry. Kaempferol is a flavonoid compound extracted from Illicium verum Hook.f. (star anise), a material that is both edible and used in traditional medicine. In this study, we evaluated the antiviral effects of kaempferol against SGIV in vitro and in vivo, and elucidated the antiviral mechanism. Our study found that kaempferol could effectively resist SGIV infection in vitro and in vivo. Kaempferol might destroy the SGIV envelope and interfere with the attachment, invasion, and replication stages of SGIV infection. Transcriptomic analysis showed that differentially expressed genes regulated by kaempferol were enriched in ribosome, NF‐κB, and phospholipase D signalling pathways. Further screening of immunity‐related genes and pathway analysis revealed that antiviral immune responses were mainly governed by the JAK–STAT, PI3K‐Akt, and TNF signalling pathways. This study demonstrated that kaempferol exhibited significant antiviral effects against SGIV through multiple mechanisms and had the potential to become an anti‐SGIV fishery drug. These findings provide a theoretical basis for the development of effective drugs for the prevention and treatment of SGIV.

Targeting Peroxiredoxin 6: Tannic Acid Inhibits Singapore Grouper Iridovirus Infection via PRDX6‐Dependent Pathway and Antioxidant Response - Xiangmou Qin; Chen‐Ao Li; Lin Huang; Qing Yu; Mingming Zhao; Yanxia Gao; Jiaxi Li; Jia Cai; Huapu Chen; Fei Ling; Junxiang Lai; Ermeng Yu; et al. (Journal of Fish Diseases, 2026)
Singapore grouper iridovirus (SGIV) is a major viral pathogen threatening grouper aquaculture. The lack of specific antiviral drugs underscores the urgent need to develop safe and effective control strategies. This study demonstrates that tannic acid (TA) exhibits significant anti‐SGIV activity in vitro. In grouper spleen (GS) cells, TA inhibited SGIV replication in a concentration‐dependent manner. Time‐of‐addition assays confirmed its antiviral efficacy when applied either before or after SGIV infection. Mechanistically, TA directly interfered with SGIV particle infectivity, viral adsorption, entry and intracellular replication. Network pharmacology analysis suggested TA's targets are associated with host cellular antioxidant pathways, among which Peroxiredoxin 6 (PRDX6) was identified as a potential target of TA. Further experiments confirmed that TA upregulated the Nrf2 antioxidant pathway and suppressed the expression of pro‐inflammatory cytokines (IL‐1β, IL‐8). Notably, TA enhanced the expression of PRDX6, and overexpression of PRDX6 significantly inhibited SGIV replication, indicating that PRDX6 contributes to the antiviral effect of TA. In vivo, TA treatment not only restored PRDX6 expression in infected groupers but also significantly reduced viral load in liver and spleen following SGIV infection. These findings demonstrate that TA inhibits SGIV through direct viral interference and PRDX6‐mediated antioxidant modulation, highlighting its potential as a natural therapeutic agent against SGIV.

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Tidal pumping modulates the dissolved organic carbon dynamics and exchange fluxes across the mangrove-fringed estuary-coast interface in Zhanjiang Bay, China - Peng Zhang; Jia Lei; Lin Zhou; Xiaoling Chen; Haowen Yu; Qing Ye; Kaixin Huang; Jibiao Zhang (Marine Environmental Research, 2026)

The Antiviral Activity and Underlying Mechanisms of Quercetin in Combating Largemouth Bass Virus Infection - Lin Huang; Wenyu Liao; Mingquan Peng; Jieying Yu; Mingzhu Liu; Junxiang Lai; Ermeng Yu; Ying Pan; Fei Ling; Shuyu Han; Qing Yu; Pengfei Li (Journal of Fish Diseases, 2026)
Largemouth bass virus (LMBV), a member of the Ranavirus genus within the Iridoviridae family, is a significant pathogen causing high mortality and substantial economic losses in largemouth bass aquaculture. Therefore, developing effective antiviral agents against this viral infection is crucial for the largemouth bass aquaculture industry. Quercetin, a widely utilised flavonoid known for its therapeutic and prophylactic properties, was investigated for its antiviral efficacy against LMBV and underlying mechanisms in this study. The results demonstrated that quercetin significantly inhibited LMBV propagation in vitro and in vivo, and was effective in both prevention and treatment stages. Specifically, quercetin at 6.25 μg/mL suppressed LMBV (major capsid protein) MCP gene transcription by up to 92.09%, with the post‐infection treatment achieving 99.33% inhibition in vitro. Mechanistic studies revealed that quercetin reduces LMBV infectivity by disrupting viral internalisation and replication, while also potentiating cellular immune responses mediated by the IFN system. In vivo experiments further confirmed that quercetin treatment reduced viral transcription in the liver, spleen and kidney by 97.49%, 47.45% and 98.42%, respectively, at 48 h post‐infection and significantly enhanced the survival rate of infected juveniles. In conclusion, quercetin demonstrated potent antiviral activity against LMBV and might serve as a promising, eco‐friendly antiviral agent.

The undescribed alkaloids from Jacobaea cannabifolia (less.) E. Wiebe and their anti-inflammatory activities - Jian-Zhe Li; Juan Pan; Yu Bi; Zhi-Chao Hao; Wei Guan; Hai-Xue Kuang; Qing-Shan Chen; Li-Li Zhang; Xin-Yue Wu; Da-Lin Li; Bing-You Yang; Yan Liu (Natural Product Research, 2026)

Optimized Midbrain Organoid Transplantation Restores Dopaminergic Nigrostriatal Pathway and Motor Function in Parkinson’s Disease Mouse Model - Lin-Bo Chen; Xin-Yu She; Xi Jiang; Peng-Jian Wu; Chang-Qing Zheng; Jun Yao (Neuroscience Bulletin, 2026)

Ethylene signaling, pathogenesis-related proteins (PRs) and SlCBF1 collectively regulate Botrytis cinerea resistance in postharvest tomato fruit under low temperature conditions - Pan Shu; Zhiyuan Wang; Bingqing Qian; Zhiyin Yu; Qinlu Zheng; Xin Yao; Hongye Fu; Yuan Qing; Xiaojuan Yin; Pan Zou; Jing Li; Lin Shen (Postharvest Biology and Technology, 2026)

Cretaceous sediment provenance, dispersal systems, and tectono-paleogeography of the western Tarim Basin, Northwest China: Far-field effects of Neo-Tethyan flat subduction - Hong-Xiang Wu; Feng-Qi Zhang; Cai-Yun Wang; Xiao-Gan Cheng; Kai-Xuan An; Yildirim Dilek; Cai Chen; Yu-Qing Zhang; Xiu-Bin Lin; Shuan-Hong Zhang; Han-Lin Chen (Global and Planetary Change, 2026)

Co-exposure to polystyrene microplastics and Di-(2-ethylhexyl) phthalate exacerbates food allergy in mice associated with gut barrier dysfunction - Xuanpei Wang; Wenfeng Liang; Shiyun Chen; Ying Liu; Jiaxin Yu; Jianing Cui; Lin Xu; Min Fang; Zhiyong Gong; Xin Liu; Qing Yang (Food Bioscience, 2026)

In vitro and in vivo evaluation of Bacillus amyloliquefaciens E35 as prophylactic agents against Singapore grouper iridovirus - Yanxia Gao; Lingling Deng; Yibing Wang; Lin Huang; Jieying Yu; Xiangmou Qin; Junxiang Lai; Ermeng Yu; Shuyuan Zhang; Ying Pan; Jiwei Xu; Qing Yu; et al. (Fish & Shellfish Immunology, 2026)

Battery swapping mode analysis for shared e-bikes from a carbon perspective - Yonggang Shen; Chenhan Lin; Yancun Song; Qing Yu; Yongping Zhang (Environmental Impact Assessment Review, 2026)

Enhancing Ore Recovery and Profitability Through Blast-Aware Dig-Limit Optimization in Open-Pit Mining - Zhi Yu; Lin-Feng Du; Zong-Xian Zhang; Ming-Qing Huang; Jian-Hua Hu; Jian Zhou; Xing-Qi Cai (Rock Mechanics and Rock Engineering, 2026)

A Non-spinal Neural Circuit for Transmitting Information of Bladder Conditions - Zhenxiang Zhu; Zhuang Liu; Zan Wang; Guangfu Cui; Mei-Yu Shi; Kunzhang Lin; Yuxiang Qiu; Tengxiao Si; Peng Chen; Qing Liu; Guo-Qiang Bi; Jie Wang; et al. (Neuroscience Bulletin, 2026)

A comprehensive review on the chemical composition, pharmacological effects and quality evaluation of Gentiana straminea Maxim. - Yuan-Wen Zhuang; Min Wang; Jian-Tao Zhao; Yu-Qing Wang; Run-Qian Yu; Huan Xia; Xiao-Hong Wei; Peng-Cheng Lin; Gui-Yang Xia; Sheng Lin (Journal of Natural Medicines, 2026)

Epigallocatechin Gallate (EGCG) Inhibits Singapore Grouper Iridovirus (SGIV) Infection by Interfering With Viral Life Cycle and Modulating Host Cell Cycle G2/M Checkpoint - Tianhong Zhao; Jinkun Xie; Chen‐Ao Li; Mingzhu Liu; Qing Yu; Lin Huang; Yanxia Gao; Mingming Zhao; Jiaxi Li; Jia Cai; Huapu Chen; Fei Ling; et al. (Journal of Fish Diseases, 2026)
Singapore grouper iridovirus (SGIV) is a highly pathogenic virus that causes substantial economic losses in marine grouper aquaculture, and effective antiviral agents are currently lacking. In this study, the anti‐SGIV activity of epigallocatechin gallate (EGCG), a natural compound from green tea, was evaluated and its underlying mechanisms were investigated. Cytotoxicity assays showed that EGCG at concentrations up to 12.5 μg/mL was safe for grouper spleen (GS) cells. EGCG treatment reduced viral MCP and VP19 mRNA expression in a dose‐dependent manner, indicating its anti‐SGIV activity. Mechanistic studies revealed that EGCG directly impaired SGIV particle infectivity and interfered with viral adsorption, entry, and intracellular replication. Network pharmacology analysis identified overlapping genes between EGCG targets and SGIV‐induced differentially expressed genes, with enrichment pathways related to cell cycle regulation, particularly the G2/M checkpoint. Further studies showed that SGIV infection upregulated the G2/M checkpoint regulators WEE1 and CHEK2, and EGCG treatment reversed these dysregulations, suggesting that EGCG alleviates SGIV‐induced G2/M arrest. In vivo, EGCG treatment significantly reduced viral load in infected groupers and improved survival rate. Collectively, these findings demonstrate that EGCG exerts potent anti‐SGIV activity both in vitro and in vivo by directly targeting multiple steps of the viral life cycle and modulating host cell cycle G2/M checkpoint pathways, highlighting its potential as a natural therapeutic agent against SGIV infection.

A novel UAV-based fusion of spectral and textural features with canopy stratification for accurate estimation of vertical nitrogen distribution in cotton - Guldana Sarsen; Qiu-xiang Tang; Ya-bin Li; Long-long Bao; Yu-hang Xu; Guang-yun Sun; Jian-wen Wu; Yierxiati Abulaiti; Qing-qing Lv; Fubin Liang; Na Zhang; Ren-song Guo; et al. (Computers and Electronics in Agriculture, 2026)

RNAi against ribosomal protein L27 gene impairs larval development in Phthorimaea operculella - Yu Zhang; Zhong-Yuan Wang; Ya-Hao Rao; Juan Peng; Lin Jin; Guo-Qing Li (Journal of Asia-Pacific Entomology, 2026)

Multifunctional Cu2O@Ag probe for ultra-sensitive SERS detection and inhibition of Escherichia coli O157: H7 - Hao Jiang; Yu-Qing Wang; Huan Cheng; Shi-Ying Fu; Hongmei Li; Jia-Sheng Lin; Yue-Jiao Zhang; Jian-Feng Li (Food Chemistry, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

Virus-host metabolic interaction: SGIV-induced protein lactylation suppresses viral propagation - Mingming Zhao; Jiaxi Li; Mingzhu Liu; Ying Pan; Sining Su; Xiangmou Qin; Yanxia Gao; Lin Huang; Junxiang Lai; Jia Cai; Huapu Chen; Qing Yu; et al. (Fish & Shellfish Immunology, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Lactiplantibacillus Plantarum O126 Postbiotics Boost growth, Antioxidant levels, Disease resistance, and Gut Health in Sea Cucumber (Apostichopus japonicus) - Feng-Li Chen; Hui-Ting Zhao; Wei Gu; Zong-Xiu Wu; Jing-Wen Xiang; Qing Yang; Yu-Lin Yang; Lei Tan; Meng-Xia Sun; Wei Cong; Shu Li; Bin-Tong Yang; et al. (Probiotics and Antimicrobial Proteins, 2026)

Three-dimensional hierarchical CuCoAl-layered double hydroxide/Ti3C2 Schottky heterojunction for efficient visible-light degradation of ciprofloxacin - Zifei Gao; Ye Liu; Deke Wang; Baoyu Zou; Xingkang Yu; Yu Dong; Qing Li; Juanjuan Ma; Lin Liu; Chao Liu; Zhiwei Tong; Jun Hu (Applied Clay Science, 2026)

In vitro and in vivo antiviral effects of myrcene on MSRV infection in largemouth bass (Micropterus salmoides) - Zhengzhao Liu; Lin Huang; Jieying Yu; Qing Yu; Mingzhu Liu; Yanxia Gao; Xiangmou Qin; Junxiang Lai; Fei Ling; Yanlei Chang; Shuyu Han; Jia Cai; et al. (Fish & Shellfish Immunology, 2026)

Preparation of cancer cell membrane-coated Gambogic acid-loaded pH-sensitive liposomes to enhance targeted anti-hepatocellular carcinoma effect - Yi-Feng Zhang; Kun Chen; Yu-Qing Zhu; Lin Liu; Xiang-Tao Kong; Yan Dai; Xiu-Juan Fu; Ya-Ling Li; Ming-Hua Liu; Dan Zhang (Drug Delivery and Translational Research, 2026)

Robigenin in combating largemouth bass ranavirus: Investigating the antiviral potency and underlying mechanisms - Wenyu Liao; Lin Huang; Jieying Yu; Mingzhu Liu; Nijia Xue; Junxiang Lai; Ermeng Yu; Fei Ling; Shuyu Han; Ying Pan; Pengfei Li; Qing Yu (Fish & Shellfish Immunology, 2026)

Assessing organic substitution thresholds in smallholder farms: Results from a 34-year experiment on crop—livestock integration systems - Yu Ning; Shuai-lin Li; Xin-hui Zhang; Zhu-qing Xia; Yun Gao; Lu Sun; Qiang Ma; Wan-tai Yu (European Journal of Agronomy, 2026)

Dorsal Column Nuclei at the Core of TENS: Circuit Principles and Outlook for Neuropathic Pain Therapy - Yi-La Ding; Xue-Qing Wu; Tian-Xin Zhao; Shi-Yao Wang; Ceng-Lin Xu; Bei Tan; Yu Du (Neuroscience Bulletin, 2026)

The GATA3-RFPL3-ASK1 axis suppresses breast cancer growth and lung metastasis - Kang Li; Chang Liu; Jun-Hui Yin; Yu-Ting He; Zhi-Zhi Xu; Wen-Jing Zhang; Jian-Qi Wang; Lu-Yao Hou; Jing Feng; Le-Min Lin; Xiu-Qing Duan; Yi Zhou; et al. (Apoptosis, 2026)

Lengthening vegetation carbon turnover time across China’s forests - Rong Ge; Xiaoli Ren; Honglin He; Guirui Yu; Li Zhang; Qian Xu; Mengyu Zhang; Shilong Piao; Kailiang Yu; Mathew Williams; Xiaobo Zhu; Shiyong Yu; et al. (Science Bulletin, 2026)

Multi-omics reveals efficient thiamethoxam biodegradation but altered flavor profile by native microbiota during Pixian broad bean paste fermentation - Xuan Yu; Siqi Huang; Jie Tang; Chuanning Peng; Qi Wen; Siqi Chen; Lanqi lei; Chenxi Yang; Yuanxi Liu; Wenliang Xiang; Qing Zhang; Hongbin Lin; et al. (International Journal of Food Microbiology, 2026)

Smartphone-assisted portable colorimetric detection of Salmonella based on a dual signal amplification mediated nanozyme cascade aptasensor - Qing Kang; Chenjing Ma; Yidi Liu; Xin Yu; Tong Lin; Jingbo Jiao; Yukun Huang; Shuo Wang; Xinjun Du (Food Bioscience, 2026)

Gibberellic acid (GA) alleviates Al toxicity in rice (Oryza sativa) through a nitric oxide (NO) dependent pathway - Qi Jiang; Hao Yu Wang; Yong Qiang Gao; Ren Fang Shen; Yi Lin Xu; Qing Song Zheng; Xiao Fang Zhu (Planta, 2026)

Degradation Pathways of Kraft Lignin by Novosphingobium sp. THN1: Insights into Refractory Dissolved Organic Matter Transformation in Lake Ecosystems - Chenyang Deng; Liwen Zhang; Chun Qing; Yuange Yu; Haorui Zhao; Genyi Wu; Yiqing Lin (Environmental Processes, 2026)

A New Species of Diaporthe Section Betulicola (Diaporthomycetidae, Diaporthales) From China - Yi Lan Jin; Xing Yu Luo; Kamran Habib; Yu Lin Ren; Qing Yang; Li Li Liu; Chanhom Loinheuang; Yang Chen; Qi Rui Li (New Zealand Journal of Botany, 2026)
A new species in Diaporthaceae, Diaporthe fengtaiensis sp. nov., is described and illustrated from Southwestern China. A comparative morpho‐anatomical study and multilocus phylogenetic analysis (ITS, CAL , HIS , TEF1‐α , TUB2 ) confirmed its position within the section Betulicola of the genus Diaporthe . The taxon is characterized by immersed ascomata (270–420 × 290–410 µm), relatively large asci (70–115 × 9.5–13.5 µm), and 1‐septate, fusiform ascospores (18.5–25.6 × 4.5–6.5 µm). Its positioning in a separate branch in the phylogenetic tree makes it distinct from the other known species of the section. A complete taxonomic treatment, based on two collected specimens, is provided along with molecular phylogenetic analyses.

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

A new sponge (Ascospongiae) from the early Cambrian Guanshan Biota - Lin-Jun Zou; Joseph P. Botting; Jie Yang; Xiao-Yu Yang; Wei Li; Qing-Hao Guo; Yu Wang; Chun-Li Li; Xi-Guang Zhang; Ai-Lin Chen (Palaeoworld, 2026)

Molecular and functional characterization of interleukin-1β in red drum (Sciaenops ocellatus) and its pivotal role in antibacterial immunity - Lin Zhang; Jinglu Ma; Jingyao Yu; Qing Chu (Fish & Shellfish Immunology, 2026)

Two birds with one stone: Constructing confined N-doped carbon catalysts to boost solar-driven interfacial water evaporation and peroxymonosulfate mediating antibiotic wastewater purification - Qi-E Zhang; Lin-Bo Deng; Hui-Qing Lv; Guo-Qing Zhao; Yan Pan; Jin Zou; Meng-Ting He; Xun-Kuan Ye; Jin-Gang Yu; Limin Lu (Environmental Research, 2026)

Warming-driven and depth-dependent responses of soil microbial communities toward nutrient limitations: Ecological insights into alpine grassland restoration - Hao Shi; Wei Wei; Jun-qiang Wang; Fei Xia; Cai-hong Yang; Lin-ling Ran; Yun-yin Xue; Hao-yang Wu; Shuang Yan; Yu Zhang; Shai-kun Zheng; Xiao-qing Qiu (Applied Soil Ecology, 2026)

Novel insights into cyanobacterial (microcystins) neurotoxicity in rats: hepatic encephalopathy - Wen-Li Xu; Liang Chen; Hui-Hui Fan; Geoffrey A. Codd; John P. Giesy; Yu-Ming Guo; Elizabeth D. Hilborn; Daniela Sedan; Darío Andrinolo; Saurabh Chatterjee; Hai-Jun Wang; Ying Liu; et al. (Archives of Toxicology, 2026)

Source-specific ecological risk assessment of heavy metal pollution in soils of an abandoned paint factory, Kaifeng City - Yu-qing Zhang; Meng-xin Zhao; Hao-lin Shi; Lin Wang; Ming Xu (Environmental Monitoring and Assessment, 2026)

Analysis of antimicrobial resistance and virulence of Vibrio parahaemolyticus - Zhu-qing Shen; Xiao-lin Zhang; Yu-qing Zhou; Meng-hua Yang; Yu-bin Su; Bo Peng (Marine Pollution Bulletin, 2026)

Single-cell RNA sequencing reveals the immune cell landscape of head kidney in the Perciform fish (Micropterus salmoides) - Zheng-Yang Zhou; Chen-Wang Lu; Zheng-Ran Jian; Shang-Jie Bai; Lin-Feng Kuang; Jin-Lai Gu; Ming-Zhu Liu; Peng-Fei Li; Gao-Xue Wang; Qing Yu; Fei Ling; Jorge Galindo-Villegas; et al. (Aquaculture, 2026)

Long-term ozone exposure and attention-deficit/hyperactivity disorder symptoms in school-aged children: Findings from a large multi-city study in China - Zhao-Huan Gui; Wan-Ting He; Yun-Ting Zhang; Joachim Heinrich; Michael S. Bloom; Shao Lin; Bin Jalaludin; Mohammed Zeeshan; Lidia Morawska; Tian-Yu Zhao; Shyamali Dharmage; Luke Knibbs; et al. (Journal of Hazardous Materials, 2026)

Electrochemical detection and electro-Fenton degradation of fipronil via Fe/Ni-BTC/MS-derived NiFe2O4@C core-shell catalyst - Yu-Qing Zhan; Cheng-Guo Liu; Jia-Jia Kou; Yi-Lin Niu; Hai-Jiao Xie; Liu Yang; Dashu Chen (Journal of Cleaner Production, 2026)

Unveiling the metabolic mechanism of pesticide in food fermentation through metagenomics and metabolomics: A case study of β-cypermethrin in Pixian broad-bean paste - Siqi Huang; Xuan Yu; Jie Tang; Chuanning Peng; Qi Wen; Siqi Chen; Lanqi lei; Chenxi Yang; Yuanxi Liu; Wenliang Xiang; Qing Zhang; Hongbin Lin; et al. (Food Chemistry, 2026)

Synergistic micro-nano composite and micron hierarchical structures enable hybrid wetting-state regulation for enhanced photothermal membrane distillation - Xiao Yu; Jia-Wei Zhu; Lin Gu; Qing-Yun Wu (Chemical Engineering Journal, 2026)

Genome-wide analysis of the sugarcane SUT gene family reveals ShSUT4 as a key regulator of abiotic stress responses - Xue-Ting Zhao; Ahmad Ali; Cui-Lian Feng; Ji-Shan Lin; Rui-Jie Wu; Shu-Zhen Zhang; Guang-Run Yu; Hai-Feng Jia; Yu-Qing Gong; Ting-Ting Zhao; Jun-Gang Wang (Theoretical and Applied Genetics, 2026)

A1-Reactive Astrocytes in the Posterior Part of Paraventricular Thalamic Nucleus Are Involved in Pain Modulation in Mice - Han-Xue Sun; Zhong-Yi Liu; Jia-Ni Li; Liu-Jie Zhao; Xue-Mei Wu; Chu-Han Liu; Jie Hong; Ke-Hua Zhu; Feng-Ling Wu; Si-Hai Chen; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2026)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Galla Chinensis as an antiviral agent: Targeting Micropterus salmoides rhabdovirus infection - Jieying Yu; Mingzhu Liu; Qing Yu; Xiangmou Qin; Mingming Zhao; Ying Pan; Nijia Xue; Hao Wang; Songlin Li; Fei Ling; Gaoxue Wang; Shuyu Han; et al. (Fish & Shellfish Immunology, 2025)

Seismic performance of precast concrete shear wall with disc spring-bolt subassembly connections - Hua-long LIU; Xun CHONG; Lin-lin XIE; Qing JIANG; Yu-long FENG; Jun-Qi HUANG (Engineering Structures, 2025)

MOF-derived core-shell MnFe2O4@C bifunctional material: Electrochemical sensing and synergistic electro-Fenton degradation of clothianidin - Jia-Jia Kou; Yu-Qing Zhan; Yi-Lin Niu; Hai-Jiao Xie; Liu Yang; Dashu Chen (Chemical Engineering Journal, 2025)

A carboxymethyl chitosan/oxidized alginate hydrogel with controlled fullerenol release accelerates diabetic wound healing through cellular senescence reprogramming - Ze-Bang Du; Qi Yuan; Ke-Jian Ni; Jie He; Jia-Shen Wu; Hai-Yan Huang; Yan-Yan Zhou; Xiao-Qing Li; Chang-Feng Zhu; Xiao-Xuan Chen; Li-Li Pan; Ran An; et al. (Chemical Engineering Journal, 2025)

A pH-responsive and nitric oxide-producing nanocarrier for targeted therapy of melanoma - Shuai Cui; Qing Yu; Ziyuan Su; Yiting Han; Sujuan Wang; Xiangyu Zou; Lin An; Nannan Yin; Hao Hong; Dongzhi Yang (Chemical Engineering Journal, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Identification, characterization, and expression profiling of rice MADS-box transcription factor genes associated with fluroxypyr-meptyl and oxyfluorfen metabolism - Zhi Zhong Zhou; Nian Hua Teng; Jia Lin Liang; Ying Yu Zeng; Yi Zhuo Wang; Li Qing Zeng; Xiao Liang Liu; Xi Ran Cheng; Zhao Jie Chen (Genetica, 2025)

Thermal runaway dynamics of LFP batteries in confined pressurized atmospheres: From triggering to gas evolution - Lin Yu; Yuhui Wang; Qing Wang; Kuo Wang; Jianqi Zhang; Xinming Qian (Chemical Engineering Journal, 2025)

Establishment of succinic acid production in recombinant Kluyveromyces marxianus enhanced by AI-guided enzyme specificity engineering and redox-controlled fermentation optimization - Du-Wen Zeng; Yi-Fan Zhu; Yuan-Hong Jiang; Ya-Hao Ding; Zhen-Zhi Wang; Kai Li; Sha Liao; Ya-Chao Fan; Lin Zhang; Yu Guang Wang; Xin-Qing Zhao (Chemical Engineering Journal, 2025)

An activatable aptamer probe Q2c for detection of grouper iridovirus - Mingzhu Liu; Jing Huang; Lin Huang; Qiwei Qin; Yanlei Chang; Lei Shi; Yun Sun; Yongcan Zhou; Shaowen Wang; Shuyu Han; Qing Yu; Pengfei Li (Aquaculture, 2025)

Effect of low-energy stirring temperature on the formation of oil-in-water emulsions stabilized by gelatin-arginine complexes - Jun Qi; Yu-cong Li; Hui-min Yan; Li-ting Zeng; Ao-jing Lv; Rui-ling Dong; Xue-qing Li; Zhou Lin; Le-le Shao; Lang Zhang; Guo-qing Duan; Chun-hui Zhang; et al. (Food Research International, 2025)

Pea protein as filler particles in dual-protein hybrid emulsified gels: Focus on the particle reinforcement theory - Peng Zhong; Qing Yu; Zonglin Guo; Hua Zheng; Jie Lin; Hongtao Lei; Yudong Shen; Shaozong Wu (Food Structure, 2025)

Integrated core-shell structured dual-mode thermoresponsive optical-electrical sensing fiber for accurate temperature recognition and early fire warning - Hualing He; Jie Xu; Md Hasib Mia; Zhonghe Yu; Yuhang Wan; Qing Jiang; Xueru Qu; Jinru Liu; Lin Hou; Yueyue Song; Zhicai Yu (Chemical Engineering Journal, 2025)

The threat of diaphragm closure to thermal runaway during battery charging - Jianqi Zhang; Tao Fan; Zhengnan Liu; Lin Yu; Yuhui Wang; FangZhou Li; Shuai Yuan; Chongye Chang; Kuo Wang; Ziwei Song; Xinming Qian; Qing Wang (Chemical Engineering Journal, 2025)

Senegenin ameliorates diabetic encephalopathy via promoting mitophagy and repressing NLRP3 inflammasome activation - Xiao-dan Yan; Yu Yang; Wan-ting Zhang; Qing-quan Kong; Xi-tong Zheng; Lin-sen Li; Qing Yu (Psychopharmacology, 2025)

Deinococcus lichenicola sp. nov., A Bacterium Isolated from a Lichen Sample - Guo-Hua Chen; Lian-Shuang Xiong; Rui Yang; Shu-Ya Zuo; Qing Yuan; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Hyperoside extends lifespan in Caenorhabditis elegans through SEK-1/PMK-1/SKN-1 pathway - Xin-Tian Yu; Lin Shi; Qiong Huang; Bao Li; Yan-Qing Li; Li-Lan Ou; Huai-Rong Luo; Gui-Sheng Wu (Biogerontology, 2025)

Geological Structural Characteristics of Subashi in West Kunlun Revealed by Aero Geophysical and Remote Sensing Data - Ming Wang; Yi-chuan Li; Hai-qing Wang; Yan-yan Wei; Xiao-xing Lin; Dao-qing Zhou; Jin-zhong Yang; Chang Zhong; Chang-chun Yu (Applied Geophysics, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Seven previously undescribed steroidal alkaloids from the fruit of Solanum nigrum L. and their biological activities - Liang-Yu Liu; Qing Peng; Yu-Ke Yang; Tong Wu; Li-Xian Chen; Li Lin (Phytochemistry, 2025)

Using ventilation hood during cooking reduced household air pollution exposure and brought cardiometabolic and pulmonary health benefits: A community-based, cluster-randomized controlled intervention study - Yueru Yang; Kuai Yu; Wending Li; Xuedan Xu; Chengyong Jia; Qi Yan; Xingxing Li; Hao Cai; Denghuan Hu; Hui Gao; Xuanwen Mu; Yuhui Lin; et al. (Journal of Hazardous Materials, 2025)

Krüppel-homolog 1 is critical for larval metamorphosis in an herbivorous ladybird - Yi-Kuan Wu; Jia-Qing Yu; Lin Jin; Guo-Qing Li (Journal of Asia-Pacific Entomology, 2025)

Characterization of IL-34 and CSF-1R in Sciaenops ocellatus: IL-34 participates in its anti-bacterial immune responses to Vibrio harveyi infection - Jiale Zhou; Jingyao Yu; Lin Zhang; Qing Chu (Fish & Shellfish Immunology, 2025)

Synergistic enhancement of wetland purification performance by introducing intermittent aeration and zero-valent iron under chilling stress - Lin-Yuan Wu; Bing-Xu Guo; Ke-Jia Zhang; Jun-Yu Ai; Wei-Yi Shi; Qing-Yuan Tian; Wen-Huai Wang; Jun-Feng Li (Chemical Engineering Journal, 2025)

Tremella fuciformis Polysaccharides Alleviate Early Brain Injury in Experimental Subarachnoid Hemorrhage by Inhibiting the KDR-Mediated P38 MAPK/NF-κB Pathway - Yu-hui Wan; Zeng-jing Cheng; Ling-xiang Fan; De-hong Yang; Bing-lin Chen; Xiang-xin Chen; Qing Zhu (Molecular Neurobiology, 2025)

Preparation of glycine-pectin complex and its application in drug delivery system - Jia-Yu Li; Meng-Yuan Zhang; Yue Chen; Yu-Qing Song; Chao-Lin Wang; Chen-Yu Zhang; Guo-Wei Yu (Natural Product Research, 2025)

Quantifying assembly processes of dissolved organic matter pools in eutrophication using high-resolution mass spectrometry and ecological models - Guan-Lin Chen; Chen Qian; Meng Du; Min-Jie Tong; Jie-Jie Chen; Han-Qing Yu (Water Research, 2025)

Whole-genome resequencing-based assessment of genomic diversity and selection signatures in Rhipicephalus microplus from Shaanxi, China - Yi-yao Mou; FU-wen Wang; YU-kun Kang; Ya-qing Li; YU-ying Yang; Tian-yuan Liu; Chu-zhao Lei; Qing Lin (Veterinary Parasitology, 2025)

Chinese Tuina ameliorates muscle damage by regulating endoplasmic reticulum stress and autophagy in a rat model of skeletal muscle contusion - Hai-chao Liu; Hao-ming Zhu; Ming Li; Bo-rui Chen; Zheng-yu Yang; Yu Wang; Shi-zhong Wang; Shao-qing Chen; Jian-ping Lin (Tissue and Cell, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Revolutionary photoelectrochemical water splitting performance of BiVO₄/Bi₂S₃ heterojunction photoanodes boosted by trace bio-Cr₂O₃ through multiple mechanisms - Yefei Su; Yang Yu; Tingting Xue; Kai Teng; Yuning Fan; Jiangjun Lin; Chang Liu; Qing Qu; Lei Li (Chemical Engineering Journal, 2025)

Stand density influences soil organic carbon stocks and fractions by mediating soil biochemical properties in Mongolian pine plantations - Yansong Zhang; De-Hui Zeng; Zimeng Sheng; Qing-Wei Wang; Dapao Yu; Guigang Lin (Plant and Soil, 2025)

miR-200b Regulates Cellular Proliferation and Inflammatory Responses by Targeting Dual-Specificity Phosphatase 1 in Lower Vertebrates, Sciaenops ocellatus - Jingyao Yu; Qing Chu; Lin Zhang (Marine Biotechnology, 2025)

Antitumor activity and mechanistic study of steroidal saponins from the rhizomes of Paris polyphylla var. yunnanensis - Yu Zhang; Yu-Chen Fan; Yu-Chen Zhang; Qing Li; Yun-Yun Su; Chen-Sen Xu; Hao-Lin Yu; Chao Wang; Jing Zhang; Zhi-Xin Liao (Phytochemistry, 2025)

A new approach to color correction and equalization for generating mars global color image mosaics from Tianwen-1 MoRIC images - Xin Ren; Xiaoxia Zhang; Wangli Chen; Wei Yan; Xingguo Zeng; Xu Tan; Xingye Gao; Qiang Fu; Lin Guo; Qing Zhang; Zhaopeng Chen; Guobin Yu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Effect of pectic polysaccharides from fresh passion fruit (Passiflora edulis f. flavicarpa L.) peel on physicochemical, texture and sensory properties of low-fat yoghurt - Ya-Hui Yu; Luo-Bang Wu; Long-Qing Li; Ming-Yu Jin; Xiaozhen Liu; Xiangying Yu; Fengyuan Liu; Yuting Li; Lin Li; Jing-Kun Yan (Food Chemistry, 2025)

Antiviral activity of epicatechin against Singapore grouper iridovirus in vitro and in vivo - Lin Huang; Jihui Kuang; Jieying Yu; Qing Yu; Weiqiang Xu; Mingzhu Liu; Yunyi Wei; Shuyu Han; Yanhua Huang; Pengfei Li (Fish & Shellfish Immunology, 2025)

Investigation on shear strength of steel-concrete-steel composite beams with lacing bars - Shi-Lin Liang; Yan-Qing Yao; Jun Yu; Chee Kiong Soh; Long Yun (Engineering Structures, 2025)

Tunable containing malononitrile AIEgens with reversible mechanochromic behaviors and promising applications - Guang Yang; Wen-Xuan Zhao; Ling Liang; Zeng-Min Xue; Fei Meng; Yu-Qing Kong; Hong-Tao Lin; Shu-Hai Chen; Chuan-Zeng Wang (Chemical Engineering Journal, 2025)

Whole-genome sequences revealed genomic diversity and selection signatures of Dermacentor silvarum in Shaanxi, China - Yi-yao Mou; Meng-ke Lin; Yu-ying Yang; Yu-kun Kang; Ya-qing Li; Tian-yuan Liu; Chu-zhao Lei; Qing Lin (Veterinary Parasitology, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Three new sesquiterpenes with cytotoxic activity from Croton tiglium - Wen-Ying Zhou; Xiao-Xiao Zheng; Yang-Mei Ou; Yang-Lin Ou; Hong-Yu Jang; Yu-Xin Peng; Yi-Yi Wang; Bi-Qing Zhao; Li Li (Phytochemistry Letters, 2025)

Photothermal cyclic self-healing coating with extended corrosion resistance utilizing Ag2S@Ti3C2 heterojunction - Wenhui Ji; Xiaohong Ji; Lin Cao; Qing Yu; Wei Wang (Journal of Environmental Chemical Engineering, 2025)

Cost-effective production of squalene using Yarrowia lipolytica via metabolic engineering and fermentation engineering - Wen-Bo Lin; Hong Chen; Ze-Qi Song; Yu-Qing Pan; Peng-Cheng Hu; Xiao-Na Yang; Xiang-Yang Lu; Yun Tian; Hu-Hu Liu (Biotechnology Letters, 2025)

The underlying mechanism of Porcine Teschovirus 2 3Cpro antagonizing the NLRP3 inflammasome - Xin-yu Zhang; Yu-ying Li; Wei Chen; Yi-min Zhou; Lin Zhou; Lu-lu Xie; Yan-Qing Hu; Hai-xin Huang; Chen-chen Zhao; Yan Qin; Tian Lan; Wen-chao Sun (Veterinary Microbiology, 2025)

Characterizing and decoding the dynamic alterations of volatile organic compounds and non-volatile metabolites of dark tea by solid-state fermentation with Penicillium polonicum based on GC–MS, GC-IMS, HPLC, E-nose and E-tongue - Xilu Zhang; Xingjun Lu; Cheng He; Yulian Chen; Yuanliang Wang; Lin Hu; Qing Qing; Mingzhi Zhu; Zhonghua Liu; Yu Xiao (Food Research International, 2025)

Collagenases from hepatopancreas and muscle of Litopenaeus vannamei: Purification, characterization and comparison of their behaviors in collagen degradation - Xu-Chen Xiao; Jia-Yin Huang; Yu-Lei Chen; Kai-Yuan Cao; Ru-Qing Yang; Duan-Quan Lin; Shu-Jun Hong; Yu-Ting Yang; Min-Jie Cao (Food Chemistry, 2025)

Interfacial clustering-derived fluorescent, mechanically strong and fire-safe epoxy composites - Dong-Qing Zeng; Xin-Miao Li; Feng Chen; Wei-Bin Bai; Yu-Cai Lin; Rong-Kun Jian (Chemical Engineering Journal, 2025)

Soil viruses regulate soil nutrient cycling through themselves and their effects on host functioning to impede the growth of continuously planted Casuarina equisetifolia - Yu-Hua Wang; Lei Hong; Yi Lin; Miao-En Qiu; Jian-Juan Li; Qing-Xu Zhang; Xiao-Li Jia; Yu-Lin Wang; Li-Yuan Wang; Yang-Xin Luo; Wen-Xiong Lin; Hai-Bin Wang; et al. (Applied Soil Ecology, 2025)

Integrated transcriptomic and metabolomic analysis of delayed leaf yellowing in postharvest pak choi (Brassica rapa subsp. chinensis) by 2-ethylhexanol (2-EH) - Mina Wang; Xiaozhen Yue; Lingda Yu; Zixin Lin; Shuzhi Yuan; Xiaodi Xu; Jinhua Zuo; Bihong Feng; Qing Wang (Postharvest Biology and Technology, 2025)

The combination of metagenomics and metabolomics reveals the effect of nitrogen fertilizer application driving the remobilization of immobilization remediation cadmium and rhizosphere microbial succession in rice - Huan-Zhan Zhou; Bu-Qing Wang; Yong-Hong Ma; Yu-Ying Sun; Huan-Lin Zhou; Zhen Song; Yuan Zhao; Wei Chen; Jie Min; Jing-Wen Li; Tao He (Journal of Hazardous Materials, 2025)

Chemical constituents from the pericarps of Zanthoxylum bungeanum Maxim. and their chemotaxonomic significance - Di-Wei Ma; Khalid Hassan Mohamed; Jian-Lin Hu; Chang-Qin Yin; Yu-Bin Wei; Xiao-Pan Chai; Qing-Bao Zhang; Lan-Chun Zhang; Jia Liu; Hao-Fei Yu (Biochemical Systematics and Ecology, 2025)

Long-term organic farming improves the red soil quality and microbial diversity in subtropics - Yongkang Wen; Wei Yao; Taobing Yu; Lang Cheng; Qing Zhang; Jida Yang; Fangding Lin; Hongye Zhu; Anna Gunina; Yadong Yang; Kevin Z. Mganga; Zhaohai Zeng; et al. (Agriculture, Ecosystems & Environment, 2025)

Rice-fish co-culture promotes multiple ecosystem services supporting increased yields - Shuang-Xi Li; Jian Jiang; Wei-Guang Lv; Evan Siemann; Ben A. Woodcock; Yu-Quan Wang; Andrea Cavalieri; Na-Ling Bai; Juan-Qin Zhang; Xian-Qing Zheng; Han-Lin Zhang; Hai-Yun Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Extraction, rapid preparation and neuroprotective effect of texasin, a main active constituent from Caragana jubata (Pall.) Poir. - Zi-Yang Xu; Qi-Jun Dai; Yu-Fan Huang; Bo-Lin Zou; Xin Lu; Jian-Bin Wang; Han-Qing Pang; Wen-Jun Xu; Liang Liu (Natural Product Research, 2025)

Five brasilane-type sesquiterpenoids with neuroprotective activities from Xylaria nigripes - Hong-Ping Long; Xi Zhou; Si-Qian Zhou; Lan-Qing Li; Ai-Lin Liang; Wen-Yu Lu; Wen-Xuan Wang; Shao Liu; Jing Li; Ji-Kai Liu (Phytochemistry, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Improving the catalytic activity and sintering resistance of Ni-BaCe0.7Zr0.1Y0.1Yb0.1O3−δ cermet anode for ammonia-fueled protonic ceramic fuel cells via Cobalt addition - Bangze Wu; Xiaole Yu; Zenan Zhao; Bingyu He; Zhanheng Jin; Zhexiang Yu; Qing Ni; Shoucheng He; Han Chen; Yifeng Zheng; Sheng Cui; Lin Ge (Chemical Engineering Journal, 2025)

Plant diversity increases diversity and network complexity rather than alters community assembly processes of leaf-associated fungi in a subtropical forest - Jie Li; Xing-Chun Li; Hui-Yun Gan; Yue Zhang; Zi-Xuan Guo; Yu-Xuan Liu; Yong-Qing Lin; Liang-Dong Guo (Science China Life Sciences, 2025)

Cholesterol suppresses AMFR-mediated PDL1 ubiquitination and degradation in HCC - Wei-Qing Shao; Yi-Tong Li; Xu Zhou; Sheng-Guo Zhang; Ming-Hao Fan; Dong Zhang; Zhen-Mei Chen; Chen-He Yi; Sheng-Hao Wang; Wen-Wei Zhu; Ming Lu; Ji-Song Chen; et al. (Molecular and Cellular Biochemistry, 2025)

Monotonic and cyclic mechanical characteristics of reconstituted soil with high liquid limit reinforced by steel slag - Cheng-Shuang Yin; Han-Lin Wang; Xiao-Ming Liu; Xiao-Qing Yu; Xin Kang; Askar Khasanov (Bulletin of Engineering Geology and the Environment, 2025)

MRI Shrimp Sign and Parietooccipital Lesion in Progressive Multifocal Leukoencephalopathy - Wen-Qian Luo; Bin Liu; Chun-Lin Yang; Ze-Yu Zhao; Guan-Qing Wang; Xiao-Li Li; Peng Zhang (The Cerebellum, 2025)

α-asarone activates mitophagy to relieve diabetic encephalopathy via inhibiting apoptosis and oxidative stress - Xiao-dan Yan; Rong-hua Fan; Yu Wang; Xiao-xu Duan; Xuan Wei; Lin-sen Li; Qing Yu (Metabolic Brain Disease, 2025)

Expanding the pH range of Fenton-like reactions for pollutant degradation: The impact of acidic microenvironments - Shi-Lin Xu; Wei Wang; Yi Song; Rui Tang; Zhen-Hu Hu; Xiao Zhou; Han-Qing Yu (Water Research, 2025)

A systematic comparative analysis of ginger-related varieties from three dimensions based on HS-SPME-GC-Q-TOF MS and UHPLC-LTQ-Orbitrap MS - Huan-ya Yang; Lin Yang; Yu-lu Wang; Yun-shu Hu; Yun Li; Hua Qu; Wen-long Wei; Hui-yan Yang; Qi-rui Bi; Jian-qing Zhang; De-an Guo (Food Research International, 2025)

A comprehensive analysis-based study of Di-(2-ethylhexyl) phthalate (DEHP)—Environmental explanation of bladder cancer progression - Fei Lin; Wen-Cai Zheng; Zhi-Bin Ke; Dong-Ning Chen; Yu-Ting Xue; Yun-Zhi Lin; Xiao-Dong Li; Qing-Shui Zheng; Yong Wei; Xue-Yi Xue; Ning Xu (Environmental Pollution, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

A simple and efficient TALEN system for genome editing in plants - Qing Liu; Lizhou Lin; Shengjian He; Jianghui Yu; Caili Xie; Chaoyue Gai; Yongqiang Han; Chunmei Liu; Feihan Huang; Daoqian Chen; Yuanyuan Song; Guannan Qin; et al. (Plant Molecular Biology, 2025)

Sesquiterpenoids from the whole plants of Elephantopus mollis with cytotoxicity activities - Qiang Lin; Jing-Yi Du; Si-Yu Yang; Zhao-Chun Zhan; Qing Tang; Hui Sun; Jin-Lin Tan; Hai-Yue Zhao; Yao-Lan Li; Yu-Bo Zhang; Guo-Cai Wang (Natural Product Research, 2025)

Dietary lecithin attenuates adverse effects of high fat diet on growth performance, lipid metabolism, endoplasmic reticulum stress and antioxidant capacity in the intestine of largemouth bass (Micropterus salmoides) - Hua Zheng; Biao Wang; Qing-Lin Li; Tao Zhao; Peng-Cheng Xu; Yu-Feng Song; Zhi Luo (Aquaculture, 2025)

Enhanced biodegradation of glyphosate by Chlorella sorokiniana engineered with exogenous purple acid phosphatase - Si-Fen Liu; Zhong-Chen Yi; Zi-Qiong Huang; Zhen-Dong Yuan; Yu-Cheng Yang; Yongteng Zhao; Qing-Yu He; Wei-Dong Yang; Hong-Ye Li; Carol Sze Ki Lin; Xiang Wang (Water Research, 2025)

Predicting the efficiency of arsenic immobilization in soils by biochar using machine learning - Jin-Man Cao; Yu-Qian Liu; Yan-Qing Liu; Shu-Dan Xue; Hai-Hong Xiong; Chong-Lin Xu; Qi Xu; Gui-Lan Duan (Journal of Environmental Sciences, 2025)

Effect of excitation voltage in a magnetically induced electric field on the physicochemical, structural and functional properties of citrus pectin - Ya-Hui Yu; Xiaozhen Liu; Luo-Bang Wu; Xiangying Yu; Ming-Yu Jin; Long-Qing Li; Fengyuan Liu; Yuting Li; Lin Li; Bing Li; Jing-Kun Yan (Food Chemistry, 2025)

Flexural behavior of reinforced concrete beams at low temperatures - Gu Xiang-Lin; Wu Jie-Ying; Yu Qian-Qian; Liu Shuang; Huang Qing-Hua (Engineering Structures, 2025)

Ground ozone rise during the 2022 shanghai lockdown caused by the unfavorable emission reduction ratio of nitrogen oxides and volatile organic compounds - Qian Wang; Yuewu Li; Fangqian Zhong; Wanqi Wu; Hongliang Zhang; Rong Wang; Yusen Duan; Qingyan Fu; Qing Li; Lin Wang; Shaocai Yu; Abdewahid Mellouki; et al. (Atmospheric Environment, 2025)

Leifsonia stereocauli sp. nov., Isolated from Stereocaulon tomentosum Fr. Lichen - Shu-Ya Zuo; Lian-Shuang Xiong; Qing Yuan; Guo-Hua Chen; Rui Yang; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Calcium regulates the physiological and molecular responses of Morus alba roots to cadmium stress - Ming-Jin Dai; Lu-Dan Zhang; Jing Li; Chun-Quan Zhu; Ling-Yu Song; He-Zi Huang; Chao-Qun Xu; Qing-Hua Li; Lin Chen; Chen-Kai Jiang; Hong-Ling Lu; Qiu-Tong Ling; et al. (Journal of Hazardous Materials, 2024)

Untargeted metabolomics and PacBio analysis on bioactive components and microbial community in co-fermentation of black soldier fly larva - He Liu; Xia Yang; Xiaolan Yu; Jiacong Lin; Shiliang Peng; Qing Li; Qingzhu Yang; Dingmei Wang; Qinfen Li (Food Research International, 2024)

Unappreciated role of secondary metabolism-derived small mediators in degrading bisphenol A and antibiotics by a laccase-expressing fungus - Kai Sun; Zi-Hao Wu; Jie Liu; Zhou-Hua Cheng; Dong-Feng Liu; Hui Lin; Han-Qing Yu (Environmental Pollution, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Chronic dietary exposure to glyphosate-induced connexin 43 autophagic degradation contributes to blood-testis barrier disruption in roosters - Qing Liang; Bao-You Liu; Tian-Lin Zhang; Hai-Jing Zhang; Yu-Long Ren; Hai-Peng Wang; Hao Wang; Lin Wang (Science of The Total Environment, 2024)

Targeted quantitative metabolomic and flavor objective quantification technique reveal the impact mechanism of shaking on black tea quality and non-volatile metabolites - Jinjin Wang; Lichi Qu; Ziming Yu; Yongwen Jiang; Chengfa Yu; Xizhe Zhu; Qingju Lin; Linchi Niu; Yaya Yu; Qing Lin; Yan Shang; Haibo Yuan; et al. (Food Chemistry, 2024)

Long-term exposure to ozone and sleep disorders in children: A multicity study in China - Zhao-Huan Gui; Joachim Heinrich; Lidia Morawska; Tian-Yu Zhao; Steve Hung-Lam Yim; Xiang-Qian Lao; Meng Gao; Duo-Hong Chen; Hui-Min Ma; Li-Zi Lin; Ru-Qing Liu; Guang-Hui Dong (Environmental Research, 2024)

Synergistic effects of metallic IrCo for promoted nitrate reduction in industrial-relevant wastewater level - Yu Tang; Pan Ran; Linjun Zhong; Haohong Liao; Qing Tong; Weixin Zou; Lin Dong (Chemical Engineering Journal, 2024)

Dielectric screening modulating charge carrier recombination in high-performance of CsPbI2Br carbon-based perovskite solar cells - Fengli Liu; Yuan Xu; Ruoshui Li; Chunyan Deng; Lin Gao; Haozhen Deng; Yu Jing; Dongbin Jiang; Qing Yao; Chenfang Zhong; Deng Wang; Jihuai Wu; et al. (Chemical Engineering Journal, 2024)

Environmental explanation of prostate cancer progression based on the comprehensive analysis of polychlorinated biphenyls - Wen-Cai Zheng; Fei Lin; Qian-Ren-Shun Qiu; Yu-Peng Wu; Zhi-Bin Ke; Shao-Hao Chen; Dong-Ning Chen; Qing-Shui Zheng; Yong Wei; Xue-Yi Xue; Ning Xu (Science of The Total Environment, 2024)

An unusual winter bloom of dinoflagellates with notable damage to kelp cultivation around Shandong peninsula, China - Hui-Xia Geng; Fan-Zhou Kong; Jin-Xiu Wang; Qing-Chun Zhang; Fang Li; Xin Hong; Min-Jie Song; Ziru Lian; Yu-Lin Cai; Ren-Cheng Yu (Marine Environmental Research, 2024)

Long-term ambient ozone exposure and childhood asthma, rhinitis, eczema, and conjunctivitis: A multi-city study in China - Zhao-Huan Gui; Zhan-Yu Guo; Yang Zhou; Shyamali Dharmage; Lidia Morawska; Joachim Heinrich; Zhang-Kai Cheng; Hui Gan; Zhi-Wei Lin; Dong-Ying Zhang; Jing-Wen Huang; Li-Zi Lin; et al. (Journal of Hazardous Materials, 2024)

Verification of Seasonal Prediction by the Upgraded China Multi-Model Ensemble Prediction System (CMMEv2.0) - Jie Wu; Hong-Li Ren; Jianghua Wan; Jingpeng Liu; Jinqing Zuo; Changzheng Liu; Ying Liu; Yu Nie; Chongbo Zhao; Li Guo; Bo Lu; Lijuan Chen; et al. (Journal of Meteorological Research, 2024)

Analysis of growth inhibition of continuously planted Casuarina equisetifolia in relation to characteristic soil microbial functions and nutrient cycling - Yu-Hua Wang; Lei Hong; Jian-Juan Li; Qing-Xu Zhang; Ai-Qi Wang; Shao-Xiong Lin; Ming-Yue Hu; Yi-Ling Chen; Wen-Xiong Lin; Hai-Bin Wang; Ze-Yan Wu (Applied Soil Ecology, 2024)

Interpenetrating LiB/Li3BN2 phases enabling stable composite lithium metal anode - Piao Qing; Shaozhen Huang; Tuoya Naren; Quan Li; Haifeng Huang; Kecheng Long; Zhijian Liu; Lin Mei; Fu Sun; Weifeng Wei; Yu Zhang; Jianmin Ma; et al. (Science Bulletin, 2024)

Expression of a novel hydrolase MhpC in Brevibacillus parabrevis BCP-09 and its characteristics for degrading synthetic pyrethroids - Yingyue Zhang; Dan Xiang; Jie Tang; Chuanning Peng; Siqi Chen; Siqi Huang; Qi Wen; Lin Liu; Wenliang Xiang; Qing Zhang; Ting Cai; Xuan Yu (Pesticide Biochemistry and Physiology, 2024)

In vitro simulated digestion and fermentation characteristics of pectic polysaccharides from fresh passion fruit (Passiflora edulis f. flavicarpa L.) peel - Ya-Hui Yu; Luo-Bang Wu; Xiaozhen Liu; Li-Chao Zhao; Long-Qing Li; Ming-Yu Jin; Xiangying Yu; Fengyuan Liu; Yuting Li; Lin Li; Jing-Kun Yan (Food Chemistry, 2024)

Investigating the impact of ultrasound on the structural, physicochemical, and emulsifying characteristics of Dioscorin: Insights from experimental data and molecular dynamics simulation - Qi Gao; Yu-qi Yang; Hao-nan Nie; Bing-qing Wang; Xue Peng; Ning Wang; Jiang-kuo Li; Jia-jia Rao; You-lin Xue (Food Chemistry, 2024)

Identification and health risk assessment of volatile and semi-volatile migrants along with chemical elements in food contact water-borne coating paper - Qing-Hua Yang; Qin-Bao Lin; Xin-Yu Hua; Jia Liao; Shi-Qiang Lu; Ling-Yan Yan; Hong-Sheng Ma (Food Packaging and Shelf Life, 2024)

Association between outdoor light at night exposure and executive function in Chinese children - Han-Yu Yang; Si-Han Wu; Shuo Zhang; Hong-Xing Zou; Le-Bing Wang; Li-Zi Lin; Zhao-Huan Gui; Xiao-Wen Zeng; Bo-Yi Yang; Ru-Qing Liu; Guang-Hui Dong; Li-Wen Hu (Environmental Research, 2024)

Insight into response mechanism of aerobic granular sludge to combined nanoparticle stress: Nitrogen removal, microbial community and heavy metal resistance genes - Yu-Qi Li; Bai-Hang Zhao; Yu-Qing Zhang; Hai-Shan Yang; Bing-Lin Zhang (Chemical Engineering Journal, 2024)

Boronate-modified electro-spun Fe doped carbon nanofibrous membrane for selective dye adsorption, catalytic degradation, and bacterial inhibition in treatment of water - De-yu Tang; Ling-ling Yan; Luo-lin Deng; Xing-han Wang; Ya-li Xiang; Qing-li Li; Juan Lin; Qing-han Zhou (Chemical Engineering Journal, 2024)

Slope displacement prediction based on multisource domain transfer learning for insufficient sample data - Hai-Qing Zheng; Lin-Ni Hu; Xiao-Yun Sun; Yu Zhang; Shen-Yi Jin (Applied Geophysics, 2024)

Pichia pastoris composition expressed aerolysin mutant of Aeromonas veronii as an oral vaccine evaluated in zebrafish (Danio rerio) - Yuan-Yuan Yao; Qing-Shuang Zhang; Shu-Bin Liu; Hong-Wei Yang; Xing-Yu Chen; Ya-Lin Yang; Chen-Chen Gao; Chao Ran; Tsegay Teame; Zhen Zhang; Zhi-Gang Zhou (Marine Life Science & Technology, 2024)
Vaccines are one of the most practical means to stop the spreading of Aeromonas veronii in aquaculture. In this study, virulence factor aerolysin mutant NTaer which has lost its hemolytic activity was used as a target antigen. Pichia pastoris constitutive secretory expression NTaer (GS115-NTaer) was used as a potential safe oral vaccine to evaluate its effectiveness on zebrafish immunity. The result shows that vaccination of GS115- NTaer for four weeks did not affect the growth performance of the host, while eliciting an effective immune protective response. Compared with the control group, the GS115-NTaer could significantly up-regulate the relative expression level of the intestinal tight junction protein 1α ( TJP1α ) gene, and significantly increased the contents of lysozyme (LYZ), complement C3 and C4 in the gut, indicating that the innate immune response of the fish was activated. The relative gene expression levels of macrophage-expressed gene 1 ( MPEG1 ) and T cell receptor ( TCR-α ) in the gut, and MPEG1 , CD4 , CD8 , TCR-α , GATA3, and T-bet in the spleen were all increased significantly, indicating that the cellular immune response of the fish was activated. Furthermore, the contents of serum IgM and intestinal mucosa IgZ antibodies were significantly increased, which showed that humoral immunity was also activated. Moreover, inoculation with GS115-NTaer significantly changed the structure of gut microbiota. In particular, the relative ratio of (Firmicutes + Fusobacteriota + Bacteroidota)/Proteobacteria was significantly higher than that of the control and GS115 groups. Lastly, the vaccinated fish were challenged with A. veronii, and the relative percent survival of GS115 and the GS115-NTear groups was 14.28% and 33.43%. This improvement of immunity was not only due to the specific immune response but also attributed to the improvement of innate immunity and the gut microbiota which was demonstrated by the germ-free zebrafish model. Collectively, this study provides information on the effectiveness of GS115-NTear as an oral vaccine for the green prevention and control of A. veronii infection in fish aquaculture.

Biphasic effects of ethanol consumption on N,N-dimethylformamide-induced liver injury in mice - Qing-Xiang Zheng; Qing-Lin Liu; Wen-Na Sun; Xin-Yu Jiang; Tao Zeng (Toxicology, 2024)

Behavioral events and functional analysis of bursicon signal during adult eclosion in the 28-spotted larger potato ladybird - Wen-Ze Li; Yi-Kuan Wu; Yu-Xing Zhang; Lin Jin; Guo-Qing Li (Pesticide Biochemistry and Physiology, 2024)

Glucoconjugated monoterpene indole alkaloids with xanthine oxidase inhibitory activity from Ophiorrhiza japonica - Bao-Bao Shi; Fan Xu; Guang-Ru Zhang; Yu He; Qing Liu; Meng-Lin Feng; Zheng-Hui Li; Ji-Kai Liu (Phytochemistry, 2024)

Genomic analysis of Alteromonas sp. M12 isolated from the Mariana Trench reveals its role in dimethylsulfoniopropionate cycling - Yue Lin; Min Zhang; Yu-Xiang Lai; Teng Liu; Meng Meng; Yan Sun; Yu Wang; Qing-Yu Dong; Chen-Xi Li; Meng-Xue Yu; Jin Cheng; Shu-Jun Liu; et al. (Marine Genomics, 2024)

Three species of rape responded to cadmium and melatonin alleviating Cd-toxicity in species-specific strategy - Xiao-long Qin; Yu-qing Zhao; De-jun Zhang; Ke-yu Wang; Wen-hui Chen; Zi-Zhong Tang; Yang-er Chen; Shu Yuan; Lin Ye; Ming Yuan (Environmental Pollution, 2024)

Surface charge accumulation of functionalized carbonized polymer dots selectively induces lysosomal membrane permeabilization of breast cancer cells - Yu Lei; Bao-Hua Tian; Xin-Xin Li; Ming-Yuan Sun; Xi-Lin Guo; Yi-Da Wang; Hui-Qing Zhou; Ri-Sheng Ma; Hai-Xia Liang (Chemical Engineering Journal, 2024)

High dimensional proteomic mapping of bone marrow immune characteristics in immune thrombocytopenia - Feng-Qi Liu; Qing-Yuan Qu; Ying Lei; Qi Chen; Yu-Xiu Chen; Meng-Lin Li; Xue-Yan Sun; Ye-Jun Wu; Qiu-Sha Huang; Hai-Xia Fu; Yuan Kong; Yue-Ying Li; et al. (Science China Life Sciences, 2024)

Repeated Ketamine Anesthesia during the Neonatal Period Impairs Hippocampal Neurogenesis and Long-Term Neurocognitive Function by Inhibiting Mfn2-Mediated Mitochondrial Fusion in Neural Stem Cells - He Huang; Ning Wang; Jia-Tao Lin; Yong-Kang Qiu; Wei-Feng Wu; Qiang Liu; Chen Chen; Hai-Bi Wang; Yan-Ping Liu; Wei Dong; Jie Wan; Hui Zheng; et al. (Molecular Neurobiology, 2024)

Two new aryltetralin-type lignans from Camellia oleifera husk - Huai-yu Cheng; Tian-qi Xu; Ya-lin Hu; Qing Shu; Wei Xu; Chun-lin Fan; Guang-xiong Zhou (Natural Product Research, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Comprehensive analysis of metal(loid)s and associated metal(loid) resistance genes in atmospheric particulate matter - Xiu-Peng Liang; He-Jing Wang; Jie-Ru Zheng; Xiao-Ru Wang; Dao-Ming Lin; Ya-Qing Wu; Rui-Lian Yu; Gong-Ren Hu; Yu Yan (Science of The Total Environment, 2024)

A 76-m per pixel global color image dataset and map of Mars by Tianwen-1 - Jianjun Liu; Xin Ren; Wei Yan; Wangli Chen; Xingguo Zeng; Xiaoxia Zhang; Xu Tan; Xingye Gao; Qiang Fu; Dingxin Liu; Lin Guo; Qing Zhang; et al. (Science Bulletin, 2024)

Combined dilute alkali and milling process enhances the functionality and gut microbiota fermentability of insoluble corn fiber - Qing Jin; Yiming Feng; Xavier Cabana-Puig; Tran N. Chau; Ronnie Difulvio; Dajun Yu; Anyang Hu; Song Li; Xin M. Luo; Jactone Ogejo; Feng Lin; Haibo Huang (Food Chemistry, 2024)

DPABINet: A toolbox for brain network and graph theoretical analyses - Chao-Gan Yan; Xin-Di Wang; Bin Lu; Zhao-Yu Deng; Qing-Lin Gao (Science Bulletin, 2024)

Estrogen-related receptor, a molecular target against lepidoptera pests - Guan Wang Shen; Die Liu; Hao Ran Xu; Lu Yu Hou; Jin Xin Wu; Qing You Xia; Ping Lin (Pesticide Biochemistry and Physiology, 2024)

Congener-specific fate and impact of microcystins in the soil-earthworm system - Bai-Lin Liu; Peng-Fei Yu; Jing-Jie Guo; Li-Si Xie; Xiang Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Nai-Xian Feng; Quan-Ying Cai; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

Experimental investigation on the flow boiling of R134a in a plate heat exchanger with mini-wavy corrugations - Wei-chao Lao; Yi-dong Fang; Qing-hu Chen; Lin-jie Xu; Hui-nan Yang; Yu-qi Huang (International Journal of Refrigeration, 2024)

Experimental and theoretical constraints on lithium isotope fractionation during brine evaporation and halite precipitation - Yongjie Lin; Marcello Merli; Paolo Censi; Simon A.T. Redfern; Yue Zhao; Qing-Zhu Yin; Mianping Zheng; Xudong Yu; Yongsheng Zhang; William J. Knapp; Edward T. Tipper (Geochimica et Cosmochimica Acta, 2024)

Ultrasound-responsive metal–organic framework-based nanosystem for sonodynamic therapy/amplified ferroptosis/IDO-blockade osteosarcoma immunotherapy - Qingjian Lei; Wei Zhou; Shijie Gao; Ningxiang Sun; Bo Wang; Haixia Yang; Jie Wang; Yu Zhao; Qing Chen; Jian Tian; Lin Cai; Feifei Yan (Chemical Engineering Journal, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Therapeutic effects and mechanisms of isoxanthohumol on DSS-induced colitis: regulating T cell development, restoring gut microbiota, and improving metabolic disorders - Ya-Na Yang; Bing Han; Mao-Qing Zhang; Na-Nan Chai; Feng-Lin Yu; Wen-Hui Qi; Meng-Yuan Tian; Dong-Zhi Sun; Ying Huang; Qing-Xin Song; Yan Li; Mao-Cui Zhu; et al. (Inflammopharmacology, 2024)

Direct aqueous photochemistry of methylglyoxal and its effect on sulfate formation - Jie Tan; Lingdong Kong; Yuwen Wang; Beibei Liu; Yixuan An; Lianghai Xia; Yu Lu; Qing Li; Lin Wang (Science of The Total Environment, 2024)

Melatonin alleviates glyphosate-induced testosterone synthesis inhibition via targeting mitochondrial function in roosters - Yu-Long Ren; Qing Liang; Cai-Yu Lian; Wei Zhang; Lin Wang (Environmental Pollution, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

Physiological and transcriptome analysis of acclimatory response to cold stress in marine red alga Pyropia yezoensis - Li-Hong Ma; Lin Tian; Yu-Qing Wang; Cong-Ying Xie; Guo-Ying Du (Algae, 2024)
Red macroalga Pyropia yezoensis is a high valuable cultivated marine crop. Its acclimation to cold stress is especially important for long cultivation period across winter in coasts of warm temperate zone in East Asia. In this study, the response of P. yezoensis thalli to low temperature was analyzed on physiology and transcriptome level, to explore its acclimation mechanism to cold stress. The results showed that the practical photosynthesis activity (indicated by ΦPSII and qP) was depressed and pigment allophycocyanin content was decreased during the cold stress of 48 h. However, the Fv/Fm and non-photochemical quenching increased significantly after 24 h, and the average growth rate of thalli also rebounded from 24 to 48 h, indicating a certain extent of acclimation to cold stress. On transcriptionally, the low temperature promoted the expression of differentially expressed genes (DEGs) related to carbohydrate metabolism and energy metabolism, while genes related to photosynthetic system were depressed. The increased expression of DEGs involved in ribosomal biogenesis and lipid metabolism which could accelerate protein synthesis and enhance the degree of fatty acid unsaturation, might help P. yezoensis thallus cells to cope with cold stress. Further co-expression network analysis revealed differential expression trends along with stress time, and corresponding hub genes play important roles in the systemic acquired acclimation to cold stress. This study provides basic mechanisms of P. yezoensis acclimation to cold temperature and may aid in exploration of functional genes for genetic breeding of economic macroalgae.

Migration of phosphorus in pig manure during pyrolysis process and slow-release mechanism of biochar in hydroponic application - Ru-Qing Jiang; Guang-Wei Yu; Lin-Hui Yu; Yu Wang; Chang-Jiang Li; Zhen-Jiao Xing; Xi-Mei Xue; Yin Wang; Cheng Yu (Science of The Total Environment, 2024)

Brunonianines A-C, C20-diterpenoid alkaloids with cyano group from Delphinium brunonianum Royle - Qing Li; Zhi-Wei Wang; Mu-Xuan Wang; Hao-Lin Yu; Lei Chen; Zhuoer Cai; Yu Zhang; Min-Min Gu; Yuan-Ling Shao; Hong-Ping Han; Zhi-Xin Liao (Phytochemistry, 2024)

Efficient capture of iodine in steam and water media by hydrogen bond-driven charge transfer complexes - Li Zhang; Yu-Ting Luo; Jia-Qi Fan; Sai-Jin Xiao; Qiong-Qing Zheng; Xiao-Lin Liu; Quan-Gen Tan; Chen Sun; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

Does saponin in quinoa really embody the source of its bitterness? - Lin Meng Song; Yuan Yu; Li Dong Du; Xue Ying Ji; Hui Gao; Yu Qing Cai; Chang Jian Li; Peng Xue (Food Chemistry, 2024)

Leaching and evolution of anthocyanins and aroma compounds during Cabernet Sauvignon wine fermentation with whole-process skin-seed contact - Xue-Chen Yao; Hua-Lin Zhang; Xin-Rui Ma; Nong-Yu Xia; Chang-Qing Duan; Wei-Ming Yang; Qiu-Hong Pan (Food Chemistry, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Cancer screening in hospitalized ischemic stroke patients: a multicenter study focused on multiparametric analysis to improve management of occult cancers - Jie Fang; Jielong Wu; Ganji Hong; Liangcheng Zheng; Lu Yu; Xiuping Liu; Pan Lin; Zhenzhen Yu; Dan Chen; Qing Lin; Chuya Jing; Qiuhong Zhang; et al. (EPMA Journal, 2024)

Virgin coconut oil: A comprehensive review of antioxidant activity and mechanisms contributed by phenolic compounds - Yu-Qing Zeng; Jin-Tao He; Bo-Yong Hu; Wen Li; Jing Deng; Qin-Lu Lin; Yong Fang (Critical Reviews in Food Science and Nutrition, 2024)

Mechanism of deltamethrin biodegradation by Brevibacillus parabrevis BCP-09 with proteomic methods. - Yingyue Zhang; Jie Tang; Su Wang; Xuerui Zhou; Chuanning Peng; Hu Zhou; Dan Wang; Haoran Lin; Wenliang Xiang; Qing Zhang; Ting Cai; Xuan Yu (Chemosphere, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

The role of a small molecular dipole moment for efficient non-doped deep blue thermally activated delayed fluorescence emitters - Hong-Ji Tan; Jie-Rong Yu; Zhi-Zhong Lin; Guo-Xi Yang; Zhi-Qiang Long; Ying-Lan Deng; Ze-Lin Zhu; Xian-Kai Chen; Jing-Xin Jian; Qing-Xiao Tong; Chun-Sing Lee (Chemical Engineering Journal, 2024)

Peroxisome Proliferator-Activated Receptor-γ Coactivator-1α in the Spotlight with Multiple Sclerosis - Ya-Na Yang; Mao-Qing Zhang; Feng-Lin Yu; Bing Han; Ming-Yue Bao; Yan He; Xing Li; Yuan Zhang (Neuroscience Bulletin, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Rare 7,9′-dinorlignans with neuroprotective activity from the roots of Lindera aggregata (Sims) Kosterm - Qian-Qing Liu; Lin-An Xiong; Jia-Yu Qian; Ting-Ting Gong; Lie-Feng Ma; Luo Fang; Zha-Jun Zhan (Phytochemistry, 2024)

Mineralogy and geochemistry of magnetite in the Zhdanov Ni-Cu-(PGE) deposit in the Pechenga ore field, Russia: Implications for the formation of magmatic sulfide ores - Qing-Lin Liang; Xie-Yan Song; Valery Smolkin; Nadezhda A. Krivolutskaya; Song-Yue Yu; Lie-Meng Chen (Journal of Asian Earth Sciences, 2024)

Expression of polyphenol oxidase of Litopenaeus vannamei and its characterization - Qian Hong; Yu-Lei Chen; Duanquan Lin; Ru-Qing Yang; Kai-Yuan Cao; Ling-Jing Zhang; Yi-Ming Liu; Le-Chang Sun; Min-Jie Cao (Food Chemistry, 2024)

Regional complex system simulation optimization through linking governance and environment performance: A case study of water environmental carrying capacity based on the SDES model - An Huang; Li Tian; Yongfu Li; Binyu Xiong; Jianghao Yu; Yuan Gao; Qing Li; Chenjing Fan; Linxiner Liu; Xuejun Duan; Chen Lin (Environmental Impact Assessment Review, 2024)

Phenotypic characteristics and immune response of Procypris merus following challenge with aquatic isolate of Klebsiella pneumoniae - Wenyu Liao; Dongdong Wei; Mingzhu Liu; Lin Huang; Bingzheng Li; Yunyi Wei; Shuyu Han; Shuaishuai Huang; Qing Yu; Pengfei Li (Journal of Fish Diseases, 2024)
Currently, aquaculture is a relatively mature industry; however, disease problems are continuously threatening the industry and hindering its development to a certain extent. Klebsiella pneumoniae is one of the zoonotic bacteria widely present in different hosts and has caused some degree of harm to the aquaculture industry, posing a potential threat to the water environment and indirectly also affecting human food safety issues. In this study, K. pneumoniae was isolated from the aquaculture environment, named as ELD, and subjected to pathogenic and immunological related studies. The results of the study showed that the strain carries at least four virulence‐related genes, magA , wabG , ureA and uge , and has developed resistance to at least seven antibacterial drugs, such as amoxicillin, doxycycline, rifampicin, and so on. Moreover, the strain is highly pathogenic and is capable of causing systemic clinical foci in Procypris merus . In addition, after infection with K. pneumoniae , the expression of IL‐1β, IL‐8, HSP70 and C2 was upregulated in P. merus as a whole, whereas the expression of TNF‐α did not change significantly in any of the tissues, which might be a kind of immune response of P. merus against K. pneumoniae infection. This study provides an important theoretical basis for the in‐depth exploration of the pathogenic mechanism of K. pneumoniae in fish and the immune response that occurs after the disease is contracted in fish, as well as theoretical support for the development of effective preventive and therapeutic strategies against K. pneumoniae ‐infected aquatic animals in the future.

Ioxynil and diethylstilbestrol impair cardiac performance and shell growth in the mussel Mytilus coruscus - Yi-Feng Li; Yue-Tong Lin; Yu-Qing Wang; Ji-Yue Ni; Deborah M. Power (Science of The Total Environment, 2023)

Limonoids from the roots of Melia azedarach and their anti-inflammatory activity - Min Song; Hui-Juan Luo; Zi-Wei Li; Ling Qiu; Yu-Xin Zhao; Cheng-Wei He; Xiao-Qi Zhang; Wen-Cai Ye; Li-Gen Lin; Qing-Wen Zhang (Phytochemistry, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Transcranial Alternating Current Stimulation in a Patient with Ataxia-Ocular Apraxia 2: a Case Report - Xiao-Ping Cheng; Wen-Hui Yu; Xia Liu; Wei Lin; Zhao-Di Wang; Xi-Chen Wang; Jun Ni; Nai-Qing Cai; Xin-Yuan Chen (The Cerebellum, 2023)

Iodine status and associated dietary factors among preschool children in Shanghai - Jing Li; Jun-Xia Liu; Yu-Qing Wang; An-Xin Lu; Yi-Hong Wang; Yin Lin; Chong-Huai Yan (Environmental Science and Pollution Research, 2023)

Unraveling heterogeneity of dissolved organic matter in highly connected natural water bodies at molecular level - Guan-Lin Chen; Chen Qian; Bo Gong; Meng Du; Rui-Zhe Sun; Jie-Jie Chen; Han-Qing Yu (Water Research, 2023)

Headspace single drop microextraction based visual colorimetry for highly sensitive, selective and matrix interference-resistant determination of sulfur dioxide in food samples - Jie Zhou; Xiaojie Lin; Li Zhao; Ke Huang; Qing Yang; Huimin Yu; Xiaoli Xiong (Food Chemistry, 2023)

Molecular and functional characterization of viperin in golden pompano, Trachinotus ovatus - Lin Huang; Xiaowen Zhu; Jihui Kuang; Bohuan Li; Qing Yu; Mingzhu Liu; Bingzheng Li; Hui Guo; Pengfei Li (Fish & Shellfish Immunology, 2023)

Oxidation of Sb(III) by Shewanella species with the assistance of extracellular organic matter - Kai-Li Wang; Di Min; Guan-Lin Chen; Dong-Feng Liu; Han-Qing Yu (Environmental Research, 2023)

Insights into the surface Structure-Sensitive photocatalytic oxidation of gaseous toluene on Pd/TiO2 catalysts - Cong Wu; Qinglong Liu; Yu Zhan; Wei Tan; Xiaoqian Wei; Qing Tong; Haiqin Wan; Lin Dong (Chemical Engineering Journal, 2023)

The modification of meteorological factors on the relationship between air pollution and periodontal diseases: an exploration based on different interaction strategies - Kai Huang; Lin-Fei Feng; Zhe-Ye Liu; Zhen-Hua Li; Yi-Cheng Mao; Xin-Qiang Wang; Jia-Wen Zhao; Kang-Di Zhang; Ying-Qing Li; Jie Wang; Wen-Jie Yu; Xin Cheng; et al. (Environmental Geochemistry and Health, 2023)

Risk assessment of mountain tourism on the Western Sichuan Plateau, China - Yu-Qing Zhang; Yue-Lin Wang; Hong Li; Xue-Ming Li (Journal of Mountain Science, 2023)

Arbuscular mycorrhiza changes plant facilitation patterns and increases resource use efficiency in intercropped annual plants - Shuang-Guo Zhu; Hai-Xia Duan; Hong-Yan Tao; Li Zhu; Rui Zhou; Yu-Miao Yang; Xiao-Lin Zhang; Wen-Ying Wang; Hao Zhu; Wei Zhang; Ren-Qing Wang; Xiu-Ping Tao; et al. (Applied Soil Ecology, 2023)

Environmental exposure to paraben and its association with blood pressure: A cross-sectional study in China - Xu Zhang; Ying Zhang; Hao Lu; Fan Yu; Xueting Shi; Bingchan Ma; Shuang Zhou; Lin Wang; Qing Lu (Chemosphere, 2023)

Mechanisms of high ammonium loading promoted phosphorus release from shallow lake sediments: A five-year large-scale experiment - Shuo-Nan Ma; Yuan-Feng Xu; Hai-Jun Wang; Hong-Zhu Wang; Yan Li; Xu-Meng Dong; Ji-Lin Xu; Qing Yu; Martin Søndergaard; Erik Jeppesen (Water Research, 2023)

Maternal transfer of F-53B inhibited neurobehavior in zebrafish offspring larvae and potential mechanisms: Dopaminergic dysfunction, eye development defects and disrupted calcium homeostasis - Luyin Wu; Mohammed Zeeshan; Yao Dang; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Yuan-Yuan Fan; Ming-Kun Sun; Tao Yu; Yue Wen; et al. (Science of The Total Environment, 2023)

Assessing the suitability of municipal sewage sludge and coconut bran as breeding medium for Oryza sativa L. seedlings and developing a standardized substrate - Linyi Lin; Jiemin Qin; Yu Zhang; Jiaxin Yin; Genmao Guo; Muhammad Amjad Khan; Yin Liu; Quan Liu; Qingqing Wang; Kenlin Chang; Ondřej Mašek; Junfeng Wang; et al. (Journal of Environmental Management, 2023)

A bispecific nanobody with high sensitivity/efficiency for simultaneous determination of carbaryl and its metabolite 1-naphthol in the soil and rice samples - Min-ling Liu; Zi-jian Chen; Xiao-qing Huang; Hong Wang; Jin-li Zhao; Yu-dong Shen; Lin Luo; Xiao-wei Wen; Bruce Hammock; Zhen-lin Xu (Environmental Pollution, 2023)

Combining HUMSC secretome and a conductive hydrogel enhances angiogenesis and electrical transmission at myocardial infarct sites to support cardiac repair - Shu-yi He; Lin-yu Long; Zhi-cun Wang; Wen-qi Liu; Wen Zhang; Cheng Hu; Xiao-feng Wu; Ruiqi Dong; Hong-song Fan; Qing-Jiang; Ying-ying Tong; Guang-hua Yang; et al. (Chemical Engineering Journal, 2023)

Self-assembled carrier-free nanomedicine suppresses tumor stemness to overcome the acquired drug-resistance of hepatocellular carcinoma - Huimin Lin; Qing Xu; Fang Zhang; Hualan Wu; Ben Hu; Guimei Chen; Xiaohua Ban; Xiaohui Duan; Meng Yu (Chemical Engineering Journal, 2023)

Heart valve-inspired self-lubricating anticoagulant surfaces - Yang Cheng; Zhiwei Yang; Xiaodan Gou; Qing Yang; Zichen Zhang; Shiyu Cui; Yuhua Ren; Lihong Fan; Haifeng Zhang; Zheng Fang; Yu Lu; Lin Kai; et al. (Chemical Engineering Journal, 2023)

GABAergic Neurons in the Nucleus Accumbens are Involved in the General Anesthesia Effect of Propofol - Jing Yan; Bei-Ning Hang; Lin-Hui Ma; Jia-Tao Lin; Yue Zhou; Xin-Hao Jiao; Ying-Xuan Yuan; Ke-Jie Shao; Le-Meng Zhang; Qi Xue; Zi-Yi Li; Hong-Xing Zhang; et al. (Molecular Neurobiology, 2023)

CAS FGOALS-f3-L Model Datasets for CMIP6 DCPP Experiment - Shuai Hu; Bo Wu; Yiming Wang; Tianjun Zhou; Yongqiang Yu; Bian He; Pengfei Lin; Qing Bao; Hailong Liu; Kangjun Chen; Shuwen Zhao (Advances in Atmospheric Sciences, 2023)
The outputs of the Chinese Academy of Sciences (CAS) Flexible Global Ocean-Atmosphere-Land System (FGOALS-f3-L) model for the decadal climate prediction project (DCPP) of the Coupled Model Intercomparison Project Phase 6 (CMIP6) are described in this paper. The FGOALS-f3-L was initialized through the upgraded, weakly coupled data assimilation scheme, referred to as EnOI-IAU, which assimilates observational anomalies of sea surface temperature (SST) and upper-level (0–1000-m) ocean temperature and salinity profiles into the coupled model. Then, nine ensemble members of 10-year hindcast/forecast experiments were conducted for each initial year over the period of 1960–2021, based on initial conditions produced by three initialization experiments. The hindcast and forecast experiments follow the experiment designs of the Component-A and Component-B of the DCPP, respectively. The decadal prediction output datasets contain a total of 44 monthly mean atmospheric and oceanic variables. The preliminary evaluation indicates that the hindcast experiments show significant predictive skill for the interannual variations of SST in the north Pacific and multi-year variations of SST in the subtropical Pacific and the southern Indian Ocean.

Carbon source shaped microbial ecology, metabolism and performance in denitrification systems - Yuan Pan; Rui-Zhe Sun; Yan Wang; Guan-Lin Chen; Ying-Ying Fu; Han-Qing Yu (Water Research, 2023)

Monitoring regional soil organic matter content using a spatiotemporal model with time-series synthetic Landsat images - Mei-Wei Zhang; Xiao-Qing Wang; Xiao-Gang Ding; Hua-Lei Yang; Qian Guo; Ling-Tao Zeng; Yu-Pei Cui; Xiao-Lin Sun (Geoderma Regional, 2023)

β-Cyclodextrin network crosslinked by novel phosphonium-based tetrakiscarboxylic acid derived from PH3 tail gas: Synthesis and application for rapid removal of organic dyes from wastewater - Yu-Lin Hong; Jian Sun; Xiu-Qin Fang; Qing-Wen Liu; Chang Wang; Cheng-Mei Liu (Carbohydrate Polymers, 2023)

Nano-pesticide carrier O-Carboxymethyl chitosan is indigestible in Apis cerana cerana and affects intestinal flora - Sheng-nan Li; Hao Wu; Rui-quan Hou; Jing-tong Zhou; Su-kun Lin; Kun-yu Zhao; Rui-fei Wang; Su-qing Huang; Zhi-xiang Zhang (Science of The Total Environment, 2023)

Semen damage contributed over 50 % to air-pollutant-induced infertility: A prospective cohort study of 3940 men in China - Ying Guo; Qing Chen; Yu Zhan; Wenzheng Zhou; Haiyan Zhang; Niya Zhou; Huan Yang; Yi Chen; Yimeng Wang; Lei Sun; Lin Ao; Jinyi Liu; et al. (Science of The Total Environment, 2023)

TMEM151A variants associated with paroxysmal kinesigenic dyskinesia - Hua lin Huang; Qing xia Zhang; Fei Huang; Xiao yan Long; Zhi Song; Bo Xiao; Guo liang Li; Cai yu Ma; Ding Liu (Human Genetics, 2023)

Obstacle avoidance based on double closed loop control of autonomous underwater vehicle for submarine cable laying - Wei-ran Wang; Zhe-hao Su; Hui-lin Ge; Xiao-Qiang Dai; Zhi-yu Zhu; Jie Yao; Qing-jun Zeng (Ocean Engineering, 2023)

Germacrane-type sesquiterpenoids from the flowers of Chrysanthemum indicum with hepatoprotective activity - Yu Liu; Fei Zhou; Hong-Zhen Shu; Li-Gen Lin; Qing-Wen Zhang (Food and Chemical Toxicology, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Correlation Analysis of Molecularly-Defined Cortical Interneuron Populations with Morpho-Electric Properties in Layer V of Mouse Neocortex - Jun-Wei Cao; Xiao-Yi Mao; Liang Zhu; Zhi-Shuo Zhou; Shao-Na Jiang; Lin-Yun Liu; Shu-Qing Zhang; Yinghui Fu; Wen-Dong Xu; Yong-Chun Yu (Neuroscience Bulletin, 2023)

Hydrogen sulfide antagonizes formaldehyde-induced ferroptosis via preventing ferritinophagy by upregulation of GDF11 in HT22 cells - Yu-Hui Tang; Lei Wu; Hong-Lin Huang; Pan-Pan Zhang; Wei Zou; Xiao-Qing Tang; Yi-Yun Tang (Toxicology, 2023)

Gestational cadmium exposure disrupts fetal liver development via repressing estrogen biosynthesis in placental trophoblasts - Yi-Ting Fu; Jin Zhang; Wei-Bo Liu; Yu-Feng Zhang; Shuang Zhang; Lu-Lu Tan; Qing Lin; Kong-Wen Ou-Yang; Yong-Wei Xiong; Wei Chang; Hao Li; Jun-Ying Yu; et al. (Food and Chemical Toxicology, 2023)

Polyethylene and polypropylene microplastics reduce chemisorption of cadmium in paddy soil and increase its bioaccessibility and bioavailability - Jing-Jie Guo; Fen Li; Hai-Chuan Xiao; Bai-Lin Liu; Lin-Nan Feng; Peng-Fei Yu; Can Meng; Hai-Ming Zhao; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Lei Xiang; et al. (Journal of Hazardous Materials, 2023)

Characteristics of changes in volatile organic compounds and microbial communities during the storage of pickles - Xi-han Sun; Xin Qi; Yu-di Han; Zhi-jun Guo; Cheng-bi Cui; Chang-qing Lin (Food Chemistry, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

The positive effects of postbiotic (SWF concentration®) supplemented diet on skin mucus, liver, gut health, the structure and function of gut microbiota of common carp (Cyprinus carpio) fed with high-fat diet - Zhe Yu; Qiang Hao; Shu-Bin Liu; Qing-Shuang Zhang; Xing-Yu Chen; Sheng-Hui Li; Chao Ran; Ya-Lin Yang; Tsegay Teame; Zhen Zhang; Zhi-Gang Zhou (Fish & Shellfish Immunology, 2023)

Click-crosslinked in-situ hydrogel improves the therapeutic effect in wound infections through antibacterial, antioxidant and anti-inflammatory activities - Xiong-Xin Lei; Chen-Yu Zou; Juan-Juan Hu; Yan-Lin Jiang; Xiu-Zhen Zhang; Long-Mei Zhao; Tao He; Qing-Yi Zhang; Ya-Xing Li; Jesse Li-Ling; Hui-Qi Xie (Chemical Engineering Journal, 2023)

High-efficient fire-safe epoxy enabled by bio-based atomic-level catalytic engineering - Lin-Yun Jiang; Zhi Li; Ya-Min Liang; Qing-Qing Bi; Song Tian; Shao-Yu Lin; Zhi Hu; Yu Zheng; Jose Hobson; De-Yi Wang (Chemical Engineering Journal, 2023)

Investigating the evolution of landscape patterns in historical subdeltas and coastal wetlands in the Yellow River Delta over the last 30 years: A geo-informatics approach - Chao Zhan; Qing Wang; Shanshan Cheng; Lin Zeng; Jiankui Yu; Cheng Dong; Xiang Yu (Frontiers in Marine Science, 2023)
Historically, the river course and coastline of the Yellow River Delta changed frequently, and many studies focused on these change trends and their driving forces. Few studies have explored the influence of historical river channels and historical coastlines on the response of modern landscape patterns. This study examines the impact of channel migration and coastline evolution on the modern landscape pattern of historical subdeltas and coastal wetlands, utilizing a combination of Geo-informatics and Remote Sensing images in 1989, 1998, 2009, and 2016. The results showed that: (1) Subdeltaic landscapes changed from 1998 to 2016, with slight changes in most landscape types in the Ancient Qing Shui Course Subdelta (AQSD), an increase in building sites by 17% in the Zhimai Course Subdelta (ZMSD), a decrease in the proportion of Phragmites/cogongrass communities by 15.8% in the Diao Kou Course Subdelta (DKSD), and domination by natural landscapes in the Modern Qing Shui Course Subdelta (MQSD). (2) Coastal wetlands also experienced changes, with an increase in cultivated land to 60% in the coastal wetlands of CWI, a decline in natural landscapes, and an increase in artificial landscapes in the coastal wetlands of CWII and CWIII, and domination by natural landscapes but an increase in salt fields and culture ponds by 3.45% in the coastal wetlands of CWIV. (3) Channel migration and coastline evolution influenced the direction of landscape succession, causing the landscape-type centroids in the entire delta to move eastward or northward. (4) Throughout the delta, the human tendency to live by rivers was observed. This was due to the availability of freshwater from these rivers, which led to the expansion of inhabited areas and man-made water bodies along the river banks. Channel migration and coastline evolution aggravated the salinization of coastal wetlands and promoted the salt industry and aquaculture in some estuaries of the Yellow River. In general, human activities play a dominant role in shaping the landscape pattern in the Yellow River Delta, but they were largely restricted to historical channel migration and historical coastline evolution.

Halogen microregulation in metal-organic frameworks for enhanced adsorption performance of ReO4-/TcO4- - Qing-Hua Hu; You-Gan Wang; Xin Gao; Yu-Zhen Shi; Sen Lin; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Spatially dual-confined metallic selenide double active centers for boosting potassium ion storage - Juan Gong; Rui Zhang; Xijun Wei; Yu Liu; Qing Luo; Qi Wan; Qiaoji Zheng; Lei Wang; Shude Liu; Dunmin Lin (Chemical Engineering Journal, 2023)

The construction of high efficient visible-light-driven 3D porous g-C3N4/Fe3O4 photocatalyst: A new photo-induced bacterial inactivation material enhanced by cascade photo-Fenton reaction - Ze-Yu Liu; Wen-Qian Huang; Chuan-Qing Huang; Zhao-Zhen Liu; Xiao-Yue Tang; Wei-Chang Chen; Zheng-Zheng Tang; Yu-Xing Huang; Shuo-Chun Zheng; Lin Lin; Changzhu Li; Yong Ye (Chemosphere, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Triclosan in paired-maternal and cord blood, and their relationships with congenital heart disease of baby - Yu-Ling Luan; Yan-Qiu Ou; Xiao-Qing Liu; Shao Lin; Ying Guo (Science of The Total Environment, 2023)

Identification of ISG15 in golden pompano, Trachinotus ovatus, and its role in virus and bacteria infections - Lin Huang; Yuan Cheng; Shuyu Han; Mingzhu Liu; Qing Yu; Hongling Wei; Jinzhao He; Pengfei Li (Fish & Shellfish Immunology, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

Association between long-term ambient ozone exposure and attention-deficit/hyperactivity disorder symptoms among Chinese children - Peien Zhou; Wangjian Zhang; Yu-Jie Xu; Ru-Qing Liu; Zhengmin Qian; Stephen Edward McMillin; Elizabeth Bingheim; Li-Zi Lin; Xiao-Wen Zeng; Bo-Yi Yang; Li-Wen Hu; Wen Chen; et al. (Environmental Research, 2023)

Recycle waste washcloth to design Fe3O4/FeS2/C heterojunction membrane as high-area capacity freestanding anode for sodium-ion batteries - Qing Lin; Shaocheng Zhang; Li-Juan Yu; Baoxiu Hou; Shuaihua Zhang; Zheng Wang; Jianjun Song; Xiaoxian Zhao (Chemical Engineering Journal, 2023)

Near-infrared I/II emission and absorption carbon dots via constructing localized excited/charge transfer state for multiphoton imaging and photothermal therapy - Wen-Bo Zhao; Dan-Dan Chen; Kai-Kai Liu; Yong Wang; Rui Zhou; Shi-Yu Song; Fu-Kui Li; Lai-Zhi Sui; Qing Lou; Lin Hou; Chong-Xin Shan (Chemical Engineering Journal, 2023)

Effects of oxygen content on gaseous and solid products during molten salt oxidation of cation exchange resins - Yun Xue; Yue-Lin Wang; Yang-Hai Zheng; Yu-Sheng Yang; Wen-Da Xu; Yong-De Yan; Ran Zhao; Qing-Guo Zhang; Xin Liu; Fu-Qiu Ma; Mi-Lin Zhang (Environmental Science and Pollution Research, 2022)

Numerical simulation of rock breaking by TBM disc cutter in soil-rock composite formations - Qing Yu; Xiaohong He; Haoyu Miao; Minghua Lin; Kaixiang Zhang; Rui Guo (Bulletin of Engineering Geology and the Environment, 2022)

GDH promotes isoprenaline-induced cardiac hypertrophy by activating mTOR signaling via elevation of α-ketoglutarate level - Zhi-Rong Lin; Zhen-Zhen Li; Yan-Jun Cao; Wen-Jing Yu; Jian-Tao Ye; Pei-Qing Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

Study on aptamer based high throughput approach identifies natural ingredients against RGNNV - Hongling Wei; Mingzhu Liu; Ke Ke; Shuangyan Xiao; Lin Huang; Qiongyu He; Changping Mo; Hai Pang; Guozhu Xiao; Pengfei Li; Qing Yu (Journal of Fish Diseases, 2022)
Nervous necrosis virus (NNV) is one of the most destructive pathogens in marine fish aquaculture and is capable of infecting more than 50 fish species worldwide, which resulted in great economic losses. Effective drugs for managing NNV infection are urgently required. Medicinal plants have been known for thousands of years and benefit of medicinal plants against pathogens in aquaculture have emerged. Nowadays, the most commonly used method for detecting virus infection and assessing antiviral drugs efficacy is reverse transcription‐quantitative real‐time PCR. However, the application is limited on account of high reagent costs, complex time‐consuming operations and long detection time. Aptamers have been widely applied in application of pathogens or diseases diagnosis and treatments because of high specificity, strong affinity, good stability, easy synthesized and low costs. This study aimed to establish an aptamer (GBN34)‐based high‐throughput screening (GBN34‐AHTS) model for efficient selection and evaluation of natural ingredients against NNV infection. GBN34‐AHTS is an expeditious rapid method for selecting natural ingredients against NNV, which is characterized with high‐speed, dram, sensitive and accurate. AHTS strategy could reduce work intensity and experimental costs and shorten the whole screening cycle of effective ingredients. AHTS should be suitable for rapid selection of effective ingredients against other viruses, which is important for improving the prevention and controlling of aquatic diseases.

Proline-mediated modulation on DNA repair pathway in rice seedlings under chromium stress by integrating gene chip and co-expression network analysis - Yu-Juan Lin; Yu-Xi Feng; Qing Zhang; Xiao-Zhang Yu (Ecotoxicology, 2022)

Two new clerodane diterpenoids and a new pyran-2-one derivative with anti-neuroinflammatory activities from Croton crassifolius - Zhi-Peng Ling; Qing Tang; Can-Jie Li; Jin-Lin Tan; Hai-Yue Zhao; Yi-Kun Hao; Zhao-Chun Zhan; Zhong-Nan Wu; Yu-Bo Zhang; Qing Zheng; Guo-Cai Wang (Journal of Natural Medicines, 2022)

Validity Analysis of the Morphological Identification of Three Highly Morphologically Similar Species Belonging to the Genus Niviventer (Rodentia: Muridae) - Yao-Yao Li; Hao-Tian Li; Jia-Wei Hao; Chen-Yi Zhang; Guan-Ze Liu; Xing-Han Lin; Xiao-Qing Sun; Guo-Chen Zang; Yu-Chun Li (Journal of Mammalian Evolution, 2022)

Catalytic effect of cesium on the oxidation behavior of cation exchange resins in Li2CO3-Na2CO3-K2CO3 melt - Yang-Hai Zheng; Yong-De Yan; Yun Xue; Yue-Lin Wang; Xin Liu; Wan-Sheng Mi; Qing-Guo Zhang; Yu Li; Fu-Qiu Ma; Mi-Lin Zhang; Zhi-Hao Gan; Kai Zhu (Environmental Science and Pollution Research, 2022)

A strategy for establishing an efficient somatic embryo regeneration system in Castanea mollissima Blume - Xiao-wei Li; Zhi-lin Sun; Yue-rong Gao; Jing-yi Ge; Yu-zhen Tian; Bing Liu; Shi-kan Sun; Ke-feng Fang; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Three new sesquiterpene lactones from the whole plants of Elephantopus scaber - Ding-Chai Lin; Qing Tang; Xue-Fang Zhuo; Wen-Zhi Wang; Can-Jie Li; Guang-Kai Kuang; Zhong-Nan Wu; Yu-Bo Zhang; Guo-Cai Wang; Yao-Lan Li (Natural Product Research, 2022)

Detection of bloom-forming dinoflagellates Karenia mikimotoi and Prorocentrum donghaiense using qPCR assays - Xiao-Kun Hu; Zhuo-Ru Lin; Qing-Chun Zhang; Fan-Zhou Kong; Jing-Yi Cen; Yu-Lan Zeng; Ren-Cheng Yu (Journal of Applied Phycology, 2022)

Identification of Key Pathways and Genes in SARS-CoV-2 Infecting Human Intestines by Bioinformatics Analysis - Ji-Chun Chen; Tian-Ao Xie; Zhen-Zong Lin; Yi-Qing Li; Yu-Fei Xie; Zhong-Wei Li; Xu-Guang Guo (Biochemical Genetics, 2022)
COVID-19 is a serious infectious disease that has recently swept the world, and research on its causative virus, SARS-CoV-2, remains insufficient. Therefore, this study uses bioinformatics analysis techniques to explore the human digestive tract diseases that may be caused by SARS-CoV-2 infection. The gene expression profile data set, numbered GSE149312, is from the Gene Expression Omnibus (GEO) database and is divided into a 24-h group and a 60-h group. R software is used to analyze and screen out differentially expressed genes (DEGs) and then gene ontology (GO) term and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses are performed. In KEGG, the pathway of non-alcoholic fatty liver disease exists in both the 24-h group and 60-h group. STRING is used to establish a protein–protein interaction (PPI) network, and Cytoscape is then used to visualize the PPI and define the top 12 genes of the node as the hub genes. Through verification, nine statistically significant hub genes are identified: AKT1, TIMP1, NOTCH, CCNA2, RRM2, TTK, BUB1B, KIF20A, and PLK1. In conclusion, the results of this study can provide a certain direction and basis for follow-up studies of SARS-CoV-2 infection of the human digestive tract and provide new insights for the prevention and treatment of diseases caused by SARS-CoV-2.

Medicinal herbs and phytochemicals to combat pathogens in aquaculture - Mengmeng Li; Dongdong Wei; Shuaishuai Huang; Lin Huang; Fengqiao Xu; Qing Yu; Mingzhu Liu; Pengfei Li (Aquaculture International, 2022)

Production of sesquiterpene patchoulol in mitochondrion-engineered Saccharomyces cerevisiae - Xin-Yi Tao; Yang-Chen Lin; Feng-Qing Wang; Qing-Hai Liu; Yu-Shu Ma; Min Liu; Dong-Zhi Wei (Biotechnology Letters, 2022)

Hippocampal SIRT1-Mediated Synaptic Plasticity and Glutamatergic Neuronal Excitability Are Involved in Prolonged Cognitive Dysfunction of Neonatal Rats Exposed to Propofol - Lin-Hui Ma; Jie Wan; Jing Yan; Ning Wang; Yan-Ping Liu; Hai-Bi Wang; Cheng-Hua Zhou; Yu-Qing Wu (Molecular Neurobiology, 2022)

The effect of preoperative statin treatment on acute kidney injury in elderly patients undergoing valve replacement surgery - Bing-qi Fu; Xue-biao Wei; Zedazhong Su; Ying-wen Lin; Zu-hui Ke; Tong Tan; Ji-yan Chen; Shou-hong Wang; Dan-qing Yu (European Journal of Clinical Pharmacology, 2022)

Mucormycosis in Mainland China: A Systematic Review of Case Reports - Lin-Wei Wei; Pei-Qiu Zhu; Xiao-Qing Chen; Jin Yu (Mycopathologia, 2022)

MAPK5 and MAPK10 overexpression influences strawberry fruit ripening, antioxidant capacity and resistance to Botrytis cinerea - Yunting Zhang; Yu Long; Yiting Liu; Min Yang; Liangxin Wang; Xiaoyang Liu; Yong Zhang; Qing Chen; Mengyao Li; Yuanxiu Lin; Haoru Tang; Ya Luo (Planta, 2022)

Termite mound formation reduces the abundance and diversity of soil resistomes - Zhen‐Zhen Yan; Qing‐Lin Chen; Chao‐Yu Li; Bao‐Anh Thi Nguyen; Yong‐Guan Zhu; Ji‐Zheng He; Hang‐Wei Hu (Environmental Microbiology, 2021)
Summary Termites are pivotal ecosystem engineers in tropical and subtropical habitats, where they construct massive nests (‘mounds’) that substantially modify soil properties and promote nutrient cycling. Yet, little is known about the roles of termite nesting activity in regulating the spread of antimicrobial resistance (AMR), one of the major Global Health challenges. Here, we conducted a large‐scale (> 1500 km) investigation in northern Australia and found distinct resistome profiles in termite mounds and bulk soils. By profiling a wide spectrum of ARGs, we found that the abundance and diversity of antibiotic resistance genes (ARGs) were significantly lower in termite mounds than in bulk soils ( P P

Precipitation increases the abundance of fungal plant pathogens in Eucalyptus phyllosphere - Qing‐Lin Chen; Hang‐Wei Hu; Zhen‐Zhen Yan; Chao‐Yu Li; Bao‐Anh Thi Nguyen; Yong‐Guan Zhu; Ji‐Zheng He (Environmental Microbiology, 2021)
Summary Understanding the current and future distributions of plant pathogens is critical to predict the plant performance and related economic benefits in the changing environment. Yet, little is known about the roles of environmental drivers in shaping the profiles of fungal plant pathogens in phyllosphere, an important habitat of microbiomes on Earth. Here, using a large‐scale investigation of Eucalyptus phyllospheric microbiomes in Australia and the multiple linear regression model, we show that precipitation is the most important predictor of fungal taxonomic diversity and abundance. The abundance of fungal plant pathogens in phyllosphere exhibited a positive linear relationship with precipitation. With this empirical dataset, we constructed current and future atlases of phyllosphere plant pathogens to estimate their spatial distributions under different climate change scenarios. Our atlases indicate that the abundance of fungal plant pathogens would increase especially in the coastal regions with up to 100‐fold increase compared with the current abundance. These findings advance our understanding of the distributions of fungal plant pathogens in phyllospheric microbiomes under the climate change, which can improve our ability to predict and mitigate their impacts on plant productivity and economic losses.

A New Instrumental Array in Sichuan, China, to Monitor Vibrations and Perturbations of the Lithosphere, Atmosphere, and Ionosphere - Chieh-Hung Chen; Yang-Yi Sun; Kai Lin; Chen Zhou; Rui Xu; Haiyin Qing; Yongxin Gao; Tao Chen; Fei Wang; Huaizhong Yu; Peng Han; Chi-Chia Tang; et al. (Surveys in Geophysics, 2021)

Sediment Coarsening in Tidal Flats and Stable Coastline of the Abandoned Southern Yellow River Sub-Delta in Response to Fluvial Sediment Flux Decrease During the Past Decades - Lin Zeng; Chao Zhan; Qing Wang; Xianbin Liu; Longsheng Wang; Xueyan Li; Xin Wang; Xiang Yu; Jinzhi Zhang; Buli Cui (Frontiers in Marine Science, 2021)
Due to remarkable reduction of sediment supply, the vulnerability of Yellow River deltaic system increased and ecological impacts occurred to some extent. To have a comprehensive and quantitative understanding of the morphological evolution of deltas, surficial sediments of tidal flat along the abandoned southern Yellow River sub-delta and two adjacent coastal units were systematically collected and evaluated by grain-size analysis in the study. The results reveal that surficial sediments of the abandoned southern Yellow River sub-delta have been coarsening significantly since the 1980s, as characterized by a decrease in both the mud content and the clay/mud ratio. In particular, the transition from cohesive to non-cohesive sediment was completed between 2007 and 2013. With a sharp decrease in sediment flux from the Yellow River estuary, the flood currents from the submarine coastal slope carry few fine particles into the tidal zone, whereas the ebb currents with reverse direction remove some fine particles from the tidal flat. This is a major cause of sediment coarsening in the tidal flat. As sediment coarsening, the coastline of the abandoned southern Yellow River sub-delta has remained stable. The significant change in the grain size of the tidal flat surficial sediments may have a profound impact on the future coastal geomorphic evolution.

Paleozoic to early Mesozoic intrusive rocks in the East Kunlun Orogenic Belt, northwestern China: petrogenesis and implications for two Tethys evolution events - Wei Xin; Qing-lin Xu; Yu-ting Zhang (Arabian Journal of Geosciences, 2021)

Human Methylmercury Exposure and Potential Impacts in Central Tibet: Food and Traditional Tibetan Medicine - Menghan Cheng; Maodian Liu; Dou Li; Qing Luo; Zhihao Zhang; Liuliang Yuan; Chenghao Yu; Han Xie; Huiming Lin; Qianru Zhang; De Ji; Xuejun Wang (Bulletin of Environmental Contamination and Toxicology, 2021)

Identification and phylogenetic analysis of five Crataegus species (Rosaceae) based on complete chloroplast genomes - Liwei Wu; Yingxian Cui; Qing Wang; Zhichao Xu; Yu Wang; Yulin Lin; Jingyuan Song; Hui Yao (Planta, 2021)

Dissociable plasticity of visual-motor system in functional specialization and flexibility in expert table tennis players - Dazhi Yin; Xuefei Wang; Xiaoyou Zhang; Qiurong Yu; Yu Wei; Qing Cai; Mingxia Fan; Lin Li (Brain Structure and Function, 2021)

Five matrine-type alkaloids from Sophora tonkinensis - Qing Tang; Ding Luo; Ding-Chai Lin; Wen-Zhi Wang; Can-Jie Li; Xue-Fang Zhuo; Zhong-Nan Wu; Yu-Bo Zhang; Guo-Cai Wang; Yao-Lan Li (Journal of Natural Medicines, 2021)

Correction to: Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

QTL mapping of the genetic basis of stem diameter in soybean - Chong-Yuan Sun; Yu-Ming Yang; Lin Jia; Xiao-Qian Liu; Huan-Qing Xu; Hai-Yan Lv; Zhong-Wen Huang; Dan Zhang (Planta, 2021)

Termite mounds reduce soil microbial diversity by filtering rare microbial taxa - Qing‐Lin Chen; Hang‐Wei Hu; Zhen‐Zhen Yan; Chao‐Yu Li; Bao‐Anh Thi Nguyen; Yong Zheng; Yong‐Guan Zhu; Ji‐Zheng He (Environmental Microbiology, 2021)
Summary Termites are ubiquitous insects in tropical and subtropical habitats, and some of them construct massive nests (‘mounds’), which substantially promote substrate heterogeneity by altering soil properties. Yet, the role of termite nesting process in regulating the distribution and diversity of soil microbial communities remains poorly understood, which introduces uncertainty in predictions of ecosystem functions of termite mounds in a changing environment. Here, by using amplicon sequencing, we conducted a survey of 134 termite mounds across >1500 km in northern Australia and found that termite mounds significantly differed from bulk soils in the microbial diversity and community compositions. Compared with bulk soils, termite nesting process decreased the microbial diversity and the relative abundance of rare taxa. Rare taxa had a narrower habitat niche breadth than dominant taxa and might be easier to be filtered by the potential intensive microbial competition during the nesting processes. We further demonstrated that the shift in pH induced by termite nesting process was a major driver shaping the microbial community profiles in termite mounds. Together, our work provides novel evidence that termite nesting is an important process in regulating soil microbial diversity, which advances our understanding of the functioning of termite mounds.

GTree: an Open-source Tool for Dense Reconstruction of Brain-wide Neuronal Population - Hang Zhou; Shiwei Li; Anan Li; Qing Huang; Feng Xiong; Ning Li; Jiacheng Han; Hongtao Kang; Yijun Chen; Yun Li; Huimin Lin; Yu-Hui Zhang; et al. (Neuroinformatics, 2021)

The adaptability of typical precipitation ensemble prediction systems in the Huaihe River basin, China - Han Wang; Ping-an Zhong; Fei-lin Zhu; Qing-wen Lu; Yu-fei Ma; Sun-yu Xu (Stochastic Environmental Research and Risk Assessment, 2021)

Datasets for the CMIP6 Scenario Model Intercomparison Project (ScenarioMIP) Simulations with the Coupled Model CAS FGOALS-f3-L - Shuwen Zhao; Yongqiang Yu; Pengfei Lin; Hailong Liu; Bian He; Qing Bao; Yuyang Guo; Lijuan Hua; Kangjun Chen; Xiaowei Wang (Advances in Atmospheric Sciences, 2021)
The datasets for the tier-1 Scenario Model Intercomparison Project (ScenarioMIP) experiments from the Chinese Academy of Sciences (CAS) Flexible Global Ocean-Atmosphere-Land System model, finite-volume version 3 (CAS FGOALS-f3-L) are described in this study. ScenarioMIP is one of the core MIP experiments in phase 6 of the Coupled Model Intercomparison Project (CMIP6). Considering future CO 2 , CH 4 , N 2 O and other gases’ concentrations, as well as land use, the design of ScenarioMIP involves eight pathways, including two tiers (tier-1 and tier-2) of priority. Tier-1 includes four combined Shared Socioeconomic Pathways (SSPs) with radiative forcing, i.e., SSP1-2.6, SSP2-4.5, SSP3-7.0 and SSP5-8.5, in which the globally averaged radiative forcing at the top of the atmosphere around the year 2100 is approximately 2.6, 4.5, 7.0 and 8.5 W m −2 , respectively. This study provides an introduction to the ScenarioMIP datasets of this model, such as their storage location, sizes, variables, etc. Preliminary analysis indicates that surface air temperatures will increase by about 1.89°C, 3.07°C, 4.06°C and 5.17°C by around 2100 under these four scenarios, respectively. Meanwhile, some other key climate variables, such as sea-ice extension, precipitation, heat content, and sea level rise, also show significant long-term trends associated with the radiative forcing increases. These datasets will help us understand how the climate will change under different anthropogenic and radiative forcings.

Three pleiotropic loci associated with bone mineral density and lean body mass - Yu-Xue Zhang; Shan-Shan Zhang; Shu Ran; Yu Liu; Hong Zhang; Xiao-Lin Yang; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; Lei Zhang; Yu-Fang Pei (Molecular Genetics and Genomics, 2021)

Improved control of Frankliniella occidentalis on greenhouse pepper through the integration of Orius sauteri and neonicotinoid insecticides - Qing-cai Lin; Hao Chen; Dirk Babendreier; Jin-ping Zhang; Feng Zhang; Xiao-yan Dai; Zuo-wen Sun; Zhao-peng Shi; Xiao-lin Dong; Guang-an Wu; Yi Yu; Li Zheng; et al. (Journal of Pest Science, 2021)

Lung injury induced by pyrrolizidine alkaloids depends on metabolism by hepatic cytochrome P450s and blood transport of reactive metabolites - Yisheng He; Wei Lian; Liang Ding; Xiaoyu Fan; Jiang Ma; Qing-Yu Zhang; Xinxin Ding; Ge Lin (Archives of Toxicology, 2021)

Identification of progranulin as a novel diagnostic biomarker for early-onset sepsis in neonates - Kai-Di Yang; Yu He; Sa Xiao; Qing Ai; Jia-Lin Yu (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Impact of prophylactic/preemptive donor lymphocyte infusion and intensified conditioning for relapsed/refractory leukemia: a real-world study - Yu Wang; Qi-Fa Liu; De-Pei Wu; Jing-Bo Wang; Xi Zhang; Heng-Xiang Wang; Feng Gao; Shun-Qing Wang; Zi-Min Sun; Jian Ouyang; Kai-Lin Xu; Su-Jun Gao; et al. (Science China Life Sciences, 2020)

Simulation and Improvements of Oceanic Circulation and Sea Ice by the Coupled Climate System Model FGOALS-f3-L - Yuyang Guo; Yongqiang Yu; Pengfei Lin; Hailong Liu; Bian He; Qing Bao; Bo An; Shuwen Zhao; Lijuan Hua (Advances in Atmospheric Sciences, 2020)

Overview of the CMIP6 Historical Experiment Datasets with the Climate System Model CAS FGOALS-f3-L - Yuyang Guo; Yongqiang Yu; Pengfei Lin; Hailong Liu; Bian He; Qing Bao; Shuwen Zhao; Xiaowei Wang (Advances in Atmospheric Sciences, 2020)
The three-member historical simulations by the Chinese Academy of Sciences Flexible Global Ocean-Atmosphere-Land System model, version f3-L (CAS FGOALS-f3-L), which is contributing to phase 6 of the Coupled Model Intercomparison Project (CMIP6), are described in this study. The details of the CAS FGOALS-f3-L model, experiment settings and output datasets are briefly introduced. The datasets include monthly and daily outputs from the atmospheric, oceanic, land and sea-ice component models of CAS FGOALS-f3-L, and all these data have been published online in the Earth System Grid Federation (ESGF, https://esgf-node.llnl.gov/projects/cmip6/ ). The three ensembles are initialized from the 600th, 650th and 700th model year of the preindustrial experiment (piControl) and forced by the same historical forcing provided by CMIP6 from 1850 to 2014. The performance of the coupled model is validated in comparison with some recent observed atmospheric and oceanic datasets. It is shown that CAS FGOALS-f3-L is able to reproduce the main features of the modern climate, including the climatology of air surface temperature and precipitation, the long-term changes in global mean surface air temperature, ocean heat content and sea surface steric height, and the horizontal and vertical distribution of temperature in the ocean and atmosphere. Meanwhile, like other state-of-the-art coupled GCMs, there are still some obvious biases in the historical simulations, which are also illustrated. This paper can help users to better understand the advantages and biases of the model and the datasets.

Tyrosine Hydroxylase Gene Polymorphisms Contribute to Opioid Dependence and Addiction by Affecting Promoter Region Function - Jun-lin Liu; Shao-qing Li; Feng Zhu; Yu-xiang Zhang; Ya-nan Wu; Jing-si Yang; Bao Zhang; Chun-xia Yan (NeuroMolecular Medicine, 2020)

Estimating purple-soil moisture content using Vis-NIR spectroscopy - Yu Gou; Jie Wei; Jin-lin Li; Chen Han; Qing-yan Tu; Chun-hong Liu (Journal of Mountain Science, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Two novel pleiotropic loci associated with osteoporosis and abdominal obesity - Lu Liu; Xiao-Lin Yang; Hong Zhang; Zi-Jia Zhang; Xin-Tong Wei; Gui-Juan Feng; Ju Liu; Hui-Ping Peng; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; et al. (Human Genetics, 2020)

A novel putative betapartitivirus isolated from the plant-pathogenic fungus Rhizoctonia solani - Yi Chen; Jia En Su; Xi Yun Qin; Zhi Yong Fan; Xiao Hai Zhang; Qing Yu; Zhen Yuan Xia; Cong Ming Zou; Gao Kun Zhao; Zhong Long Lin (Archives of Virology, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

The Potential Role of PKA/CREB Signaling Pathway Concerned with Gastrodin Administration on Methamphetamine-Induced Conditioned Place Preference Rats and SH-SY5Y Cell Line - Gen-Meng Yang; Lu Li; Feng-Lin Xue; Chen-Li Ma; Xiao-Feng Zeng; Yong-Na Zhao; Dong-Xian Zhang; Yang Yu; Qian-Wen Yan; Yi-Qing Zhou; Shi-Jun Hong; Li-Hua Li (Neurotoxicity Research, 2020)

Endometrial autophagy is essential for embryo implantation during early pregnancy - Yan Su; Juan-Juan Zhang; Jun-Lin He; Xue-Qing Liu; Xue-Mei Chen; Yu-Bin Ding; Chao Tong; Chuan Peng; Yan-Qing Geng; Ying-Xiong Wang; Ru-Fei Gao (Journal of Molecular Medicine, 2020)

lncRNA-XIST protects the hypoxia-induced cardiomyocyte injury through regulating the miR-125b-hexokianse 2 axis - Ji-Lin Fan; Ting-Ting Zhu; Zhen-Yu Xue; Wen-Qing Ren; Jing-Qi Guo; Heng-Yi Zhao; Shi-Liang Zhang (In Vitro Cellular & Developmental Biology - Animal, 2020)

Development of Climate and Earth System Models in China: Past Achievements and New CMIP6 Results - Tianjun Zhou; Ziming Chen; Liwei Zou; Xiaolong Chen; Yongqiang Yu; Bin Wang; Qing Bao; Ying Bao; Jian Cao; Bian He; Shuai Hu; Lijuan Li; et al. (Journal of Meteorological Research, 2020)

Agrobacterium-mediated genetic transformation of Chinese chestnut (Castanea mollissima Blume) - Zhi-lin Sun; Xiao Li; Wan Zhou; Jun-di Yan; Yue-rong Gao; Xiao-wei Li; Jia-chen Sun; Ke-feng Fang; Qing Zhang; Yu Xing; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Chinese chestnut ( Castanea mollissima ) is an important germplasm resource for the breeding of Castanea species worldwide with vital ecological and economic value. Biotechnology overcomes the limitations of traditional breeding and accelerates germplasm improvement. However, a genetic transformation system for Chinese chestnut has not yet been established. In this study, a stable and efficient Agrobacterium -mediated genetic transformation method for Chinese chestnut is described. Embryogenic calli of C. mollissima cv. ‘Yanshanhongli’ were used as the target material. The sensitivity of embryogenic calli to kanamycin was determined, whereby the proliferation of non-transformed calli was completely inhibited at 180 mg/L. Antibiotic inhibition results for Chinese chestnut embryogenic calli showed that 50 mg/L cefotaxime and 500 μM timentin completely inhibited the growth of Agrobacterium tumefaciens but did not affect the normal growth of Chinese chestnut embryogenic calli. When embryogenic calli were co-cultured for 2 days with Agrobacterium tumefaciens strain AGL1 harboring the PBI121-EGFP plasmid, an embryogenic callus transformation efficiency of 4.55% was obtained, and two transgenic chimera were acquired. This Agrobacterium -mediated transformation system for Chinese chestnut provides a fundamental platform for genetic improvement of core germplasm and for further verification of gene function.

Characteristics and Prognosis of Talaromyces marneffei Infection in Non-HIV-Infected Children in Southern China - Jing Guo; Bing-Kun Li; Tian-Min Li; Fang-Lin Wei; Yu-Jiao Fu; Yan-Qing Zheng; Kai-Su Pan; Chun-Yang Huang; Cun-Wei Cao (Mycopathologia, 2019)

Association between social health status and depressive symptoms among community-dwelling elderly adults in Zhejiang Province, China - Hong-lei Dai; Zhe-bin Yu; Liu-qing You; Min-hua Fan; Hong-wei Zhu; Dan-jie Jiang; Meng-yin Wu; Shu-juan Lin; Xiao-cong Zhang; Kun Chen (Journal of Zhejiang University-SCIENCE B, 2019)

Association of Genetic Polymorphisms with Age at Onset in Han Chinese Patients with Bipolar Disorder - Shao-Hua Hu; Yu-Qing Han; Ting-Ting Mou; Man-Li Huang; Jian-Bo Lai; Chee H Ng; Jing Lu; Qiao-Qiao Lu; Qiu-Yan Lin; Yu-Zhi Zhang; Jian-Bo Hu; Ning Wei; et al. (Neuroscience Bulletin, 2019)

Involvement of glutamate receptors in regulating calcium influx in rice seedlings under Cr exposure - Yan-Hong Li; Xiao-Zhang Yu; Ling-Yun Mo; Yu-Juan Lin; Qing Zhang (Ecotoxicology, 2019)

Interaction of cyanate uptake by rice seedlings with nitrate assimilation: gene expression analysis - Xiao-Zhang Yu; Sheng-Yu Lei; Yu-Juan Lin; Qing Zhang (Environmental Science and Pollution Research, 2019)

Intragenic Transcriptional cis-Antagonism Across SLC6A3 - Ying Zhao; Jinlong Yu; Juan Zhao; Xiaowu Chen; Nian Xiong; Tao Wang; Hong Qing; Zhicheng Lin (Molecular Neurobiology, 2019)

Transcriptome analysis of Oryza sativa in responses to different concentrations of thiocyanate - Yu-Juan Lin; Xiao-Zhang Yu; Qing Zhang (Environmental Science and Pollution Research, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Atorvastatin ameliorates the contractile dysfunction of the aorta induced by organ culture - Feng Zhou; Fang Rao; You-Qing Deng; Hui Yang; Su-Juan Kuang; Fei-Long Wu; Shu-Lin Wu; Yu-Mei Xue; Xiao-Mu Wu; Chun-Yu Deng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

The analgesic effect and possible mechanisms by which koumine alters type II collagen-induced arthritis in rats - Gui-Lin Jin; Jian Yang; Wan-Qing Chen; Jie Wang; Hong-Qiang Qiu; Ying Xu; Chang-Xi Yu (Journal of Natural Medicines, 2019)

Expansion and evolutionary patterns of GDSL-type esterases/lipases in Rosaceae genomes - Yunpeng Cao; Yahui Han; Dandan Meng; Muhammad Abdullah; Jiangliu Yu; Dahui Li; Qing Jin; Yi Lin; Yongping Cai (Functional & Integrative Genomics, 2018)

Assessment of anti-diabetic activity of peanut shell polyphenol extracts - Xiao-meng Sun; Hai-qing Ye; Jing-bo Liu; Lei Wu; Ding-bo Lin; Ya-li Yu; Feng Gao (Journal of Zhejiang University-SCIENCE B, 2018)

Deformation process and mechanism analyses for a planar sliding in the Mayanpo massive bedding rock slope at the Xiangjiaba Hydropower Station - Shi-lin Zhang; Zhao-hui Zhu; Shun-chao Qi; Yu-xiang Hu; Qing Du; Jia-wen Zhou (Landslides, 2018)

Temporal and Spatial Variations of Microbial Carbon Utilization in Water Bodies from the Dajiuhu Peatland, Central China - Rui-Cheng Wang; Hong-Mei Wang; Xing Xiang; Yu Gao; Qing-Wei Song; Lin-Feng Gong (Journal of Earth Science, 2018)

pTAC10, an S1-domain-containing component of the transcriptionally active chromosome complex, is essential for plastid gene expression in Arabidopsis thaliana and is phosphorylated by chloroplast-targeted casein kinase II - Qing-Bo Yu; Tuan-Tuan Zhao; Lin-Shan Ye; Ling Cheng; Ying-Qian Wu; Chao Huang; Zhong-Nan Yang (Photosynthesis Research, 2018)

Expression of BC1 Impairs Spatial Learning and Memory in Alzheimer’s Disease Via APP Translation - Tongmei Zhang; Pei Pang; Zemin Fang; Yu Guo; Hao Li; Xinyan Li; Tian Tian; Xin Yang; Wenting Chen; Shu Shu; Na Tang; Jianhua Wu; et al. (Molecular Neurobiology, 2018)

AZI23’UTR Is a New SLC6A3 Downregulator Associated with an Epistatic Protection Against Substance Use Disorders - Kefu Liu; Jinlong Yu; Juan Zhao; Yanhong Zhou; Nian Xiong; Jie Xu; Tao Wang; Richard L. Bell; Hong Qing; Zhicheng Lin (Molecular Neurobiology, 2018)

Identification of a mutation in CNNM4 by whole exome sequencing in an Amish family and functional link between CNNM4 and IQCB1 - Sisi Li; Quansheng Xi; Xiaoyu Zhang; Dong Yu; Lin Li; Zhenyang Jiang; Qiuyun Chen; Qing K. Wang; Elias I. Traboulsi (Molecular Genetics and Genomics, 2018)

A Quninolylthiazole Derivatives as an ICT-Based Fluorescent Probe of Hg(II) and its Application in Ratiometric Imaging in Live HeLa Cells - Jian-Ying Bai; Yu-Zhong Xie; Chang-Jiang Wang; Shu-Qing Fang; Lin-Nan Cao; Ling-Li Wang; Jing-Yi Jin (Journal of Fluorescence, 2018)

Mobile carbon supply in trees and shrubs at the alpine treeline ecotone - Qing-Wei Wang; Cheng-Gang Liu; Wangming Zhou; Lin Qi; Li Zhou; Dapao Yu; Limin Dai (Plant Ecology, 2018)

Microphytoplankton community structure in the western Arctic Ocean: surface layer variability of geographic and temporal considerations in summer - Yu Wang; Peng Xiang; Jian-hua Kang; You-yin Ye; Geng-ming Lin; Qing-liang Yang; Mao Lin (Hydrobiologia, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

Genetic analysis of three porcine bocaparvoviruses and identification of a natural recombinant breakpoint in NS1 - Yu Zhou; Jia Xu; Shi-Kang Zhu; Qing-Feng Meng; Zhi-Xiong Lin; Ru Chen; Ai-Dong Qian (Archives of Virology, 2018)

Cyclooxygenase-2 (COX-2) polymorphism rs689466 may contribute to the increased susceptibility to post-traumatic osteomyelitis in Chinese population - Lei Wang; Nan Jiang; Qing-rong Lin; Cheng-he Qin; Yan-jun Hu; Bin Yu (Infectious Diseases, 2017)

Two new phenylpropanoids from Swertia atroviolacea and their anti-5 α -reductase activity - Hai-Yan Wu; Xue-Qing Kan; Yu Sheng; Lin-Yun Mou; Qing-Song Yang; Qiu-Feng Hu; Gan-Peng Li (Natural Product Research, 2017)

A new diphenyl ether derivative from Mirabilis himalaica - Si-Yu Zhou; Guo-Wei Wang; Yan-Lin Zou; Li-Qing Deng; Ming-Xu Liu; Zhi-Hua Liao; Xiao-Zhong Lan; Min Chen (Natural Product Research, 2017)

Genetic Variants of Microtubule Actin Cross-linking Factor 1 (MACF1) Confer Risk for Parkinson’s Disease - Xin Wang; Nuomin Li; Nian Xiong; Qi You; Jie Li; Jinlong Yu; Hong Qing; Tao Wang; Heather J. Cordell; Ole Isacson; Jeffery M. Vance; Eden R. Martin; et al. (Molecular Neurobiology, 2017)

Overexpression of a chrysanthemum transcription factor gene DgNAC1 improves the salinity tolerance in chrysanthemum - Ke Wang; Ming Zhong; Yin-huan Wu; Zhen-yu Bai; Qian-yu Liang; Qing-lin Liu; Yuan-zhi Pan; Lei Zhang; Bei-bei Jiang; Yin Jia; Guang-li Liu (Plant Cell Reports, 2017)

Associations Between Hepatic Functions and Plasma Amyloid-Beta Levels—Implications for the Capacity of Liver in Peripheral Amyloid-Beta Clearance - Ye-Ran Wang; Qing-Hua Wang; Tao Zhang; Yu-Hui Liu; Xiu-Qing Yao; Fan Zeng; Jing Li; Fa-Yin Zhou; Lin Wang; Jia-Chuan Yan; Hua-Dong Zhou; Yan-Jiang Wang (Molecular Neurobiology, 2017)

A Missense Variant in TREML2 Reduces Risk of Alzheimer’s Disease in a Han Chinese Population - Teng Jiang; Yu Wan; Jun-Shan Zhou; Meng-Shan Tan; Qing Huang; Xi-Chen Zhu; Huan Lu; Hui-Fu Wang; Qi Chen; Lin Tan; Ying-Dong Zhang; Lan Tan; et al. (Molecular Neurobiology, 2017)

Plasma Amyloid-Beta Levels in Patients with Different Types of Cancer - Wang-Sheng Jin; Xian-Le Bu; Yu-Hui Liu; Lin-Lin Shen; Zhen-Qian Zhuang; Shu-Sheng Jiao; Chi Zhu; Qing-Hua Wang; Hua-Dong Zhou; Tao Zhang; Yan-Jiang Wang (Neurotoxicity Research, 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

Inhibitory Effect of Endomorphin-2 Binding to the μ-Opioid Receptor in the Rat Pre-Bötzinger Complex on the Breathing Activity - Jian Qi; Hui Li; Ting-Bao Zhao; Ya-Cheng Lu; Ting Zhang; Jin-Lian Li; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2017)

Detection of genotoxic effects of drinking water disinfection by-products using Vicia faba bioassay - Yu Hu; Li Tan; Shao-Hui Zhang; Yu-Ting Zuo; Xue Han; Na Liu; Wen-Qing Lu; Ai-Lin Liu (Environmental Science and Pollution Research, 2017)

Minocycline ameliorates d-galactose-induced memory deficits and loss of Arc/Arg3.1 expression - Xu Li; Fen Lu; Wei Li; Jun Xu; Xiao-Jing Sun; Ling-Zhi Qin; Qian-Lin Zhang; Yong Yao; Qing-Kai Yu; Xin-Liang Liang (Molecular Biology Reports, 2016)

Combined effects of age and polymorphisms in Notch3 in the pathogenesis of cerebral infarction disease - Chun-Yu Zhu; Yue Wang; Qing-Xuan Zeng; Yu Qian; Huan Li; Zi-Xia Yang; Ya-Mei Yang; Qiong Zhang; Fei-Feng Li; Shu-Lin Liu (Metabolic Brain Disease, 2016)

Trabala Vishnou Gigantina Yang (Lepidoptera: Lasiocampidae) Larval Fitness on six Sympatric Plant Species in Sea-Buckthorn Forest - Dong-Mei Wen; Lin-Feng Yu; Yong-Hua Liu; Xiong-Fei Yan; Peng-Fei Lu; You-Qing Luo (Journal of Insect Behavior, 2016)

Low temperature destruction of PCDD/Fs over V2O5-CeO2/TiO2 catalyst with ozone - Ming-feng Yu; Xiao-qing Lin; Mi Yan; Xiao-dong Li; Tong Chen; Jian-hua Yan (Environmental Science and Pollution Research, 2016)

Catalytic destruction of PCDD/Fs over vanadium oxide-based catalysts - Ming-feng Yu; Xiao-qing Lin; Xiao-dong Li; Mi Yan; Bayu Prabowo; Wen-wei Li; Tong Chen; Jian-hua Yan (Environmental Science and Pollution Research, 2016)

Anisotropic Drained Deformation Behavior and Shear Strength of Natural Soft Marine Clay - Yu-Ke Wang; Lin Guo; Yu-Feng Gao; Yue Qiu; Xiu-Qing Hu; Ying Zhang (Marine Georesources & Geotechnology, 2016)

Education and Risk of Dementia: Dose-Response Meta-Analysis of Prospective Cohort Studies - Wei Xu; Lan Tan; Hui-Fu Wang; Meng-Shan Tan; Lin Tan; Jie-Qiong Li; Qing-Fei Zhao; Jin-Tai Yu (Molecular Neurobiology, 2016)

Paraventricular Nucleus Infusion of Epigallocatechin-3-O-Gallate Improves Renovascular Hypertension - Qiu-Yue Yi; Jie Qi; Xiao-Jing Yu; Hong-Bao Li; Yan Zhang; Qing Su; Tao Shi; Dong-Mei Zhang; Jing Guo; Zhi-Peng Feng; Mo-Lin Wang; Guo-Qing Zhu; et al. (Cardiovascular Toxicology, 2016)

Reverse transcription genome exponential amplification reaction assay for rapid and universal detection of human rhinoviruses - Li Guan; Lin-Qing Zhao; Hang-Yu Zhou; Kai Nie; Xin-Na Li; Dan Zhang; Juan Song; Yuan Qian; Xue-Jun Ma (Archives of Virology, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

Mechanism Underlying the Analgesic Effect Exerted by Endomorphin-1 in the rat Ventrolateral Periaqueductal Gray - Tao Chen; Jing Li; Ban Feng; Rui Hui; Yu-Lin Dong; Fu-Quan Huo; Ting Zhang; Jun-Bin Yin; Jian-Qing Du; Yun-Qing Li (Molecular Neurobiology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Deep-Water Sedimentary Characteristics and Response in the Reed Area of the Southern South China Sea - Zheng Hong-Bo; Yan Pin; Yan-Lin Wang; Yu-Qing Xing (Marine Georesources & Geotechnology, 2016)

Sex Dimorphism Profile of Alzheimer’s Disease-Type Pathologies in an APP/PS1 Mouse Model - Shu-Sheng Jiao; Xian-Le Bu; Yu-Hui Liu; Chi Zhu; Qing-Hua Wang; Lin-Lin Shen; Cheng-Hui Liu; Ye-Ran Wang; Xiu-Qing Yao; Yan-Jiang Wang (Neurotoxicity Research, 2016)

Tumor MICA status predicts the efficacy of immunotherapy with cytokine-induced killer cells for patients with gastric cancer - Yu Chen; Wan-song Lin; Wei-feng Zhu; Jing Lin; Zhi-feng Zhou; Chuan-zhong Huang; Gang Chen; Yi Shi; Zeng-qing Guo; Yun-bin Ye (Immunologic Research, 2016)

Distinct subcellular localization and potential role of LINE1-ORF1P in meiotic oocytes - Yi-Bo Luo; Li Zhang; Zi-Li Lin; Jun-Yu Ma; Jialin Jia; Suk Namgoong; Qing-Yuan Sun (Histochemistry and Cell Biology, 2016)

Serum Amyloid-Beta Levels are Increased in Patients with Chronic Obstructive Pulmonary Disease - Xian-Le Bu; Guo-Qiang Cao; Lin-Lin Shen; Yang Xiang; Shu-Sheng Jiao; Yu-Hui Liu; Chi Zhu; Fan Zeng; Qing-Hua Wang; Ye-Ran Wang; Yong He; Hua-Dong Zhou; et al. (Neurotoxicity Research, 2015)

Retraction Note to: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2015)

The diversity of coral associated bacteria and the environmental factors affect their community variation - Yan-Ying Zhang; Juan Ling; Qing-Song Yang; You-Shao Wang; Cui-Ci Sun; Hong-Yan Sun; Jing-Bin Feng; Yu-Feng Jiang; Yuan-Zhou Zhang; Mei-Lin Wu; Jun-De Dong (Ecotoxicology, 2015)

Effect of antioxidants and light stabilisers on silver migration from nanosilver-polyethylene composite packaging films into food simulants - Qi-Zhi Su; Qin-Bao Lin; Chao-Fang Chen; Yu-Mei Wu; Li-Bing Wu; Xiao-Qing Chen; Zhi-Wei Wang (Food Additives & Contaminants: Part A, 2015)

Associations Between ApoEε4 Carrier Status and Serum BDNF Levels—New Insights into the Molecular Mechanism of ApoEε4 Actions in Alzheimer’s Disease - Yu-Hui Liu; Shu-Sheng Jiao; Ye-Ran Wang; Xian-Le Bu; Xiu-Qing Yao; Yang Xiang; Qing-Hua Wang; Lin Wang; Juan Deng; Jing Li; Xin-Fu Zhou; Hua-Dong Zhou; et al. (Molecular Neurobiology, 2015)

Association between tobacco use and the upper gastrointestinal microbiome among Chinese men - Emily Vogtmann; Roberto Flores; Guoqin Yu; Neal D. Freedman; Jianxin Shi; Mitchell H. Gail; Bruce A. Dye; Guo-Qing Wang; Vanja Klepac-Ceraj; Bruce J. Paster; Wen-Qiang Wei; Hui-Qin Guo; et al. (Cancer Causes & Control, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Activation of Extracellular Signal-Regulated Kinase1/2 in the Medial Prefrontal Cortex Contributes to Stress-Induced Hyperalgesia - Jian Qi; Chen Chen; Ya-Cheng Lu; Ting Zhang; Hao Xu; Yuan-Yuan Cui; Yan-Zhou Chen; Wen Wang; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2014)

Identifying candidate genes for discrimination of ulcerative colitis and Crohn’s disease - Lian-Jie Lin; Ying Zhang; Yan Lin; Yu Jin; Chang-Qing Zheng (Molecular Biology Reports, 2014)

Effects of Bone Marrow Mesenchymal Stem Cells on Hematopoietic Recovery and Acute Graft-Versus-Host Disease in Murine Allogeneic Umbilical Cord Blood Transplantation Model - Zhen Yu Li; Chun Qing Wang; Guang Lu; Xiu Ying Pan; Kai Lin Xu (Cell Biochemistry and Biophysics, 2014)

RETRACTED ARTICLE: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2014)

Quantitative trait loci analysis of individual and total isoflavone contents in soybean seeds - HAI JUN ZHANG; JING WEN LI; YA JING LIU; WEN ZHU JIANG; XING LIN DU; LIN LI; XIAO WEI Li; LIAN TAI SU; QING YU WANG; YING WANG (Journal of Genetics, 2014)

Investigation of key microRNAs associated with hepatocellular carcinoma using small RNA-seq data - Lian-Jie Lin; Yan Lin; Yu Jin; Chang-Qing Zheng (Molecular Biology Reports, 2014)

Polymorphisms of pentanucleotide repeats (tttta)n in the promoter of CYP11A1 and their relationships to polycystic ovary syndrome (PCOS) risk: a meta-analysis - Min Yu; Ruizhi Feng; Xiaoxi Sun; Haojue Wang; Huan Wang; Qing Sang; Li Jin; Lin He; Lei Wang (Molecular Biology Reports, 2014)

Combined effects of acute thermal and hypo-osmotic stresses on osmolality and hsp70, hsp90 and sod expression in the sea cucumber Apostichopus japonicus Selenka - Qing-lin Wang; Shan-shan Yu; Chuan-xin Qin; Shuang-lin Dong; Yun-wei Dong (Aquaculture International, 2014)

MiR-200a is involved in proliferation and apoptosis in the human endometrial adenocarcinoma cell line HEC-1B by targeting the tumor suppressor PTEN - Rong Li; Jun-lin He; Xue-mei Chen; Chun-Lan Long; De-Hui Yang; Yu-Bin Ding; Hong-Bo Qi; Xue-Qing Liu (Molecular Biology Reports, 2014)

Microscopic research on a multi-source traditional Chinese medicine, Astragali Radix - Kun-Zi Yu; Jing Liu; Bao-Lin Guo; Zhong-Zhen Zhao; Hao Hong; Hu-Biao Chen; Shao-Qing Cai (Journal of Natural Medicines, 2014)

Inactivation kinetics of formaldehyde on N-acetyl-β-d-glucosaminidase from Nile tilapia (Oreochromis niloticus) - Wei-Ni Zhang; Ding-Ping Bai; Xin-Yu Lin; Qing-Xi Chen; Xiao-Hong Huang; Yi-Fan Huang (Fish Physiology and Biochemistry, 2014)

The first complete genomic characterization of an Amur virus isolate from China - Yu Zhang; Bo-Hua Liu; Fang Lin; Yong-Guo Zhang; Bing-Yin Si; Xiao-Ping Kang; Yi Hu; Jing Li; Xiao-Yan Wu; Yu-Chang Li; Qing-Yu Zhu; Yin-Hui Yang (Archives of Virology, 2013)

The effects of the codon usage and translation speed on protein folding of 3Dpol of foot-and-mouth disease virus - Xiao-xia Ma; Yu-ping Feng; Jun-lin Liu; Bing Ma; Li Chen; Yong-qing Zhao; Peng-hui Guo; Jun-zhen Guo; Zhong-ren Ma; Jie Zhang (Veterinary Research Communications, 2013)

Molecular detection and genomic characterization of Torque teno sus virus 1 and 2 from domestic pigs in central China - Kun Li; Lin-Qing Wang; Yu-Yang Wu; An-Jun Chao; Quan-Wei Lu; Zhan-Yong Wei; Bao-An Cui; Hong-Ying Chen (Virus Genes, 2013)

The Flexible Global Ocean-Atmosphere-Land system model, Spectral Version 2: FGOALS-s2 - Qing Bao; Pengfei Lin; Tianjun Zhou; Yimin Liu; Yongqiang Yu; Guoxiong Wu; Bian He; Jie He; Lijuan Li; Jiandong Li; Yangchun Li; Hailong Liu; et al. (Advances in Atmospheric Sciences, 2013)

The flexible global ocean-atmosphere-land system model, Grid-point Version 2: FGOALS-g2 - Lijuan Li; Pengfei Lin; Yongqiang Yu; Bin Wang; Tianjun Zhou; Li Liu; Jiping Liu; Qing Bao; Shiming Xu; Wenyu Huang; Kun Xia; Ye Pu; et al. (Advances in Atmospheric Sciences, 2013)

The active alkaloids of Gelsemium elegans Benth. are potent anxiolytics - Ming Liu; Hui-Hui Huang; Jian Yang; Yan-Ping Su; Hong-Wei Lin; Li-Qing Lin; Wei-Jian Liao; Chang-Xi Yu (Psychopharmacology, 2013)

Suggestion of GLYAT gene underlying variation of bone size and body lean mass as revealed by a bivariate genome-wide association study - Yan-Fang Guo; Li-Shu Zhang; Yong-Jun Liu; Hong-Gang Hu; Jian Li; Qing Tian; Ping Yu; Feng Zhang; Tie-Lin Yang; Yan Guo; Xiang-Lei Peng; Meng Dai; et al. (Human Genetics, 2013)

Novel differential transcript expression identified by LongSAGE in the mouse endometrium during the implantation window - Yu-Bin Ding; Jun-Lin He; Xue-Mei Chen; Xue-Qing Liu; Ying-Xiong Wang (Molecular Biology Reports, 2013)

The Response of Soil Nematode Community to Nitrogen, Water, and Grazing History in the Inner Mongolian Steppe, China - Wei-bin Ruan; Yuan Sang; Qing Chen; Xiang Zhu; Shan Lin; Yu-bao Gao (Ecosystems, 2012)

Multi-environment mapping and meta-analysis of 100-seed weight in soybean - Ya-nan Sun; Jun-bo Pan; Xiang-lin Shi; Xiang-yu Du; Qiong Wu; Zhao-ming Qi; Hong-wei Jiang; Da-wei Xin; Chun-yan Liu; Guo-hua Hu; Qing-shan Chen (Molecular Biology Reports, 2012)

The dissection and SSR mapping of a high-temperature adult-plant stripe rust resistance gene in American spring wheat cultivar Alturas - Lei Zhao; Jing Feng; Chun-Yu Zhang; Xiao-Dan Xu; Xian-Ming Chen; Quan Sun; Qing Miao; Shi-Chang Xu; Feng Lin (European Journal of Plant Pathology, 2012)

A new triterpenoid saponin from Gynostemma pentaphyllum - Lin Shi; Xian-Jun Meng; Jia-Qing Cao; Yu-Qing Zhao (Natural Product Research, 2012)

Gastrectomy and risk of pancreatic cancer: systematic review and meta-analysis of observational studies - Yuanfeng Gong; Quanbo Zhou; Yu Zhou; Qing Lin; Bing Zeng; Rufu Chen; Zhihua Li (Cancer Causes & Control, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Biodegradation of bensulfuron-methyl and its effect on bacterial community in paddy soils - Xiao-Yan Lin; Yu-Yi Yang; Yu-Hua Zhao; Qing-Lin Fu (Ecotoxicology, 2012)

miR-15b and miR-16 regulate TNF mediated hepatocyte apoptosis via BCL2 in acute liver failure - Fangmei An; Bangdong Gong; Hui Wang; Dongshan Yu; Gangde Zhao; Lanyi Lin; Weiliang Tang; Hong Yu; Shisan Bao; Qing Xie (Apoptosis, 2012)

Production of cloned transgenic cow expressing omega-3 fatty acids - Xia Wu; Hongsheng Ouyang; Biao Duan; Daxin Pang; Li Zhang; Ting Yuan; Lian Xue; Daibang Ni; Lei Cheng; Shuhua Dong; Zhuying Wei; Lin Li; et al. (Transgenic Research, 2012)

Risk stratification of spontaneous bacterial peritonitis in cirrhosis with ascites based on classification and regression tree analysis - Ke-Qing Shi; Yu-Chen Fan; Li Ying; Xian-Feng Lin; Mei Song; Ling-Fei Li; Xie-Yan Yu; Yong-Ping Chen; Ming-Hua Zheng (Molecular Biology Reports, 2012)

The expression level of Rosa Terminal Flower 1 (RTFL1) is related with recurrent flowering in roses - Li-Na Wang; Yun-Feng Liu; Yu-Man Zhang; Rong-Xiang Fang; Qing-Lin Liu (Molecular Biology Reports, 2012)

Three-dimensional interpretation of sparse survey line MT data: Synthetic examples - Chang-Hong Lin; Han-Dong Tan; Qing Shu; Tuo Tong; Yu-Mei Zhang (Applied Geophysics, 2012)

Strontium Ranelate Prevents Bone Loss in a Rat Model of Localized Muscle Paralysis - Zhi-Feng Sheng; Yu-Lin Ma; Dejun Tong; De-Yu Fang; Qing-Chun Liang; Li-Hong Liu; Jian Zhang; Er-Yuan Liao (Annals of Biomedical Engineering, 2012)

FTH1 binds to Daxx and inhibits Daxx-mediated cell apoptosis - Fang Liu; Zhi-Yin Du; Jun-Lin He; Xue-Qing Liu; Qiu-Bo Yu; Ying-Xiong Wang (Molecular Biology Reports, 2012)

The unsaturation of phosphatidylglycerol in thylakoid membrane alleviates PSII photoinhibition under chilling stress - Xiao-lin Sun; Sha Yang; Li-Yan Wang; Qiu-Yu Zhang; Shi-Jie Zhao; Qing-Wei Meng (Plant Cell Reports, 2011)

Green Preference Enhances the Attractiveness of and Promotes Feeding on NaCl Resource in the Yellow-spined Bamboo Locust, Ceracris kiangsu - Hai-Ping Yu; Zhi-Tian Wang; Kai Xiao; Lin Shao; Guo-Qing Li (Journal of Insect Behavior, 2010)

Cloning and characterization of a potato TFL1 gene involved in tuberization regulation - Jian-Lin Guo; Chun-Lin Yu; Chun-Yuan Fan; Qi-Neng Lu; Jing-Ming Yin; Yun-Feng Zhang; Qing Yang (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

The functional expression of calcium-sensing receptor in the differentiated THP-1 cells - Yu-hui Xi; Hong-zhu Li; Wei-hua Zhang; Li-na Wang; Li Zhang; Yan Lin; Shu-zhi Bai; Hong-xia Li; Ling-yun Wu; Rui Wang; Chang-qing Xu (Molecular and Cellular Biochemistry, 2010)

Novel microRNAs in silkworm (Bombyx mori) - Yimei Cai; Xiaomin Yu; Qing Zhou; Caixia Yu; Haiyan Hu; Jiucheng Liu; Hongbin Lin; Jin Yang; Bing Zhang; Peng Cui; Songnian Hu; Jun Yu (Functional & Integrative Genomics, 2010)

Over-expression of the AtGA2ox8 gene decreases the biomass accumulation and lignification in rapeseed (Brassica napus L.) - Xiao-ying Zhao; Deng-feng Zhu; Bo Zhou; Wu-sheng Peng; Jian-zhong Lin; Xing-qun Huang; Re-qing He; Yu-hong Zhuo; Dan Peng; Dong-ying Tang; Ming-fang Li; Xuan-ming Liu (Journal of Zhejiang University-SCIENCE B, 2010)

The physiological response and sub-cellular localization of lead and cadmium in Iris pseudacorus L. - Yu-Qing Zhou; Su-Zhen Huang; Shi-Long Yu; Ji-Guang Gu; Jiu-Zhou Zhao; Yu-Lin Han; Jia-Jia Fu (Ecotoxicology, 2010)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

Digenic inheritance of non-syndromic deafness caused by mutations at the gap junction proteins Cx26 and Cx31 - Xue-Zhong Liu; Yongyi Yuan; Denise Yan; Emilie Hong Ding; Xiao Mei Ouyang; Yu Fei; Wenxue Tang; Huijun Yuan; Qing Chang; Li Lin Du; Xin Zhang; Guojian Wang; et al. (Human Genetics, 2009)

A novel genetic locus for familial febrile seizures and epilepsy on chromosome 3q26.2–q26.33 - Xiao-Hua Dai; Wen-Wu Chen; Xu Wang; Qi-Hui Zhu; Cong Li; Lin Li; Mu-Gen Liu; Qing-K. Wang; Jing-Yu Liu (Human Genetics, 2008)

Iron contributes to the formation of catechol isoquinolines and oxidative toxicity induced by overdose dopamine in dopaminergic SH-SY5Y cells - Ran Wang; Hong Qing; Xiao-Qian Liu; Xiao-Lin Zheng; Yu-Lin Deng (Neuroscience Bulletin, 2008)

Stereoselective glucuronidation of carvedilol by Chinese liver microsomes - Lin-ya You; Chun-na Yu; Sheng-gu Xie; Shu-qing Chen; Su Zeng (Journal of Zhejiang University-SCIENCE B, 2007)

Cellular and molecular responses in progressive pseudorheumatoid dysplasia articular cartilage associated with compound heterozygous WISP3 gene mutation - Hou-De Zhou; Yan-Hong Bu; Yi-Qun Peng; Hui Xie; Min Wang; Lin-Qing Yuan; Yi Jiang; Duo Li; Qi-You Wei; Yu-Ling He; Tao Xiao; Jiang-Dong Ni; et al. (Journal of Molecular Medicine, 2007)

Role of P-glycoprotein in Limiting the Brain Penetration of Glabridin, An Active Isoflavan from the Root of Glycyrrhiza glabra - Xi-Yong Yu; Shu-Guang Lin; Zhi-Wei Zhou; Xiao Chen; Jun Liang; Xue-Qing Yu; Balram Chowbay; Jing-Yuan Wen; Wei Duan; Eli Chan; Xiao-Tian Li; Jie Cao; et al. (Pharmaceutical Research, 2007)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

Expression of truncated phosphoproteins of Nipah virus and Hendra virus in Escherichia coli for the differentiation of henipavirus infections - Ji-Ming Chen; Koon Chu Yaiw; Meng Yu; Lin-Fa Wang; Qing-Hua Wang; Gary Crameri; Zhi-Liang Wang (Biotechnology Letters, 2007)

Localization of vesicular glutamate transporters in the peripheral vestibular system of rat - Yuan Wang; You-Wang Pang; Yu-Lin Dong; Fu-Xing Zhang; Jin-Lian Li; Yun-Qing Li (Neuroscience Bulletin, 2007)

Role of tumor metastasis suppressor gene KAI1 in digestive tract carcinomas and cancer cells - Qiao Wu; Yuan Ji; Ming-qing Zhang; Yu-qiang Chen; Fu Chen; Da-lin Shi; Zong-hui Zheng; Yao-jian Huang; Wen-jin Su (Cell and Tissue Research, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)